Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Molecular epidemiology and antimicrobial resistance of Vibrio parahaemolyticus isolates from aquatic products in the Southern Fujian coast, China - Qiao-Hua Zheng; Yang Chen; Yu-Fang Tian; Turmidzi Fath; Jun-Chao Zheng; Dan-Feng Zhang; Yi-Hong Wang; Qing-Sen Chen; Feng-Xia Li; Xiu-Min Chen; Yuan-Qing Hu (Brazilian Journal of Microbiology, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Generation, characteristics, and resource recovery of copper smelting solid wastes: A review - Yun Li; Yiwei Deng; Xiaobo Min; Lin Tian; Changhao He; Yunyan Wang; Yong Ke; Cong Peng; Min Chen (Chemical Engineering Journal, 2026)

Effects of cellulase treatment on properties and functional performances of hardwood-like lignocellulose-based biochar and its modified derivatives - Kai Yang; Kang Wang; Wenyan Xie; Wenjuan Wang; Wen Tao Li; Jing Cao; Jing Wang; Han Tang; Min-tian Gao; Jiajun Hu; Jixiang Li (Bioresource Technology, 2026)

Temporal germination of lettuce under salinity and nano-silicon: A high-throughput phenomics framework with deep learning - Mohamed Ahmed Moustafa; Min Kang; Xiuqing Fu; Luxu Tian; Hanghang Li; Penghong Shen; Ziyi Zhang; Jianzhe Zhou; ChenXu Zhu; Junxiang Cheng; Sanglu Yang; Ahmed Elsayed Mahmoud Fodah; et al. (Plant Science, 2026)

Electro-enhanced nonradical peroxydisulfate activation over graphitic carbon-supported single-atom iron for ciprofloxacin mineralization - Shifeng Li; Zimeng Wang; Yu Tian; Mengran Chu; Shuhua Yao; Min Xiao; Juan Yang (Journal of Environmental Chemical Engineering, 2026)

Colloidal biochar promotes microbial carbon dioxide fixation and enhances net soil organic carbon gain - Jia Bing Liu; Jia Wang; Wang Kai Tong; Han Tang; Mei Ru Yue; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Mixed-gas nanobubble and colloidization stacked modification: Enhancing porous/chemical properties and endowing rapid adsorption function of biochar - Mei Ru Yue; Han Tang; Wang Kai Tong; Jia Bing Liu; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Cooperative regulation of hydrogen-bond-donor configuration and spatial effects in triazine-based ionic polymers for the cycloaddition of CO2 with epoxides - Lizhen Zhu; Shuangjiang Li; Min Li; Yiyan Liu; Debiao Tian; Penglu Zhong; Yunfei Zhi; Kaili Yao; Canyue Zhang; Manoj Pudukudy; Shaoyun Shan; Yi Liu (Journal of Environmental Chemical Engineering, 2026)

Increasing stand density promoted soil organic carbon sequestration by improving necromass carbon accumulation in Robinia pseudoacacia plantations - Min Zhao; Yue Zhang; Yuchen Li; Jia Tian (Forest Ecology and Management, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Dry mafic recharge modulates degassing in rift-related magma reservoirs recorded by a giant porphyry Mo system - Wen-Tian Li; Shao-Yong Jiang; M. Wiedenbeck; Hao-Xiang Zhang; Yan-Liang Yin; Hui-Min Su (Earth and Planetary Science Letters, 2026)

An elastic polyester-fish scale scaffold for sequential-release of biofactors to facilitate bone regeneration in postmenopausal osteoporosis with diabetes - Junwu Wang; Lanhong Guo; Wenjie Zhao; Shuai Chen; Yilong Huang; Tian Luan; Hao Chen; Peng Ma; Wen Min; Jinghuan Huang; Jingfeng Li (Chemical Engineering Journal, 2026)

Identification, characterization and biogenic fungicide screening of Macrophomina phaseolina (Tassi) Goid. causing root rot in Atractylodes lancea (Thunb.) DC. - Haonan Shen; Ruixin Ju; Ang Li; Min Tang; Xiaomeng Fei; Yueyu Ye; Lixia Wang; Fang Tian; Wei Gu (Australasian Plant Pathology, 2026)

Spatially distributed modeling of biofilm-induced hydrodynamic evolution in porous media - Hongcheng Zhang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Wang Kai Tong; Jia Jie Zou; Min-tian Gao; Zhi Li; Xihua Wang; Yalei Zhang; Kah Hon Leong; Swee Pin Yeap; et al. (Journal of Hydrology, 2026)

Surfactants promote microbial CO2 fixation by enhancing nutrient utilization - Jia Wang; Piao Yi Jiang; Jia Bing Liu; Wang Kai Tong; Han Tang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Sciences, 2026)

Ultimate removal of refractory organics in coking wastewater by integrated sustainable oxidation and adsorption processes - Yunxing Dong; Lili Zhang; Weihan Tian; Lele Gao; Shumin Li; Yingxin Gao; Min Yang (Journal of Environmental Sciences, 2026)

Solid-state fermentation of waste herbal medicine residues by a novel rumen-derived probiotic consortium for valorization and microbial-metabolite shifts - Junda Li; Jie Xu; Piao Wei; Hanxuan Gong; Min Tian; Weijie Yan; Caiying Ma; Dmitry Il; Yuxin Yang (Bioresource Technology, 2026)

Impacts of concentrated leachate recirculation on methane production suppression, odorous gas emissions, and salinity accumulation in municipal solid waste - Yu-Xiang Zhang; Xuan-Qi Zhang; Wen-Jie Xu; Han Ke; Ji-Wu Lan; Yun-Min Chen; Tian Qi; Yao-Huang Li; Xue Cai (Waste Management, 2026)

Retraction notice to "Asiatic acid reverses cisplatin resistance in A549/DDP cells by activating the P38 MAPK/slug pathway" [Tissue Cell 98 (2026) 103145] - Min Yu; Qian Zhang; Wenli Shang; Shenghong Wei; Hongxia Wen; Shufen Huo; Xiang Li; Xuan Li; Heng Zhang; Yingxuan Tian (Tissue and Cell, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Fe/N Co-doped sludge-derived biochar enables rapid Maduramicin adsorption via coupled hydrophobic partitioning and Fe–N complexation - Xinying Li; Huilin Wan; Zhifu Tian; Min Ji; Siyuan Zhai; Qinghua Ouyang; Na Lin; Yingxin Zhao (Journal of Environmental Chemical Engineering, 2026)

Assessing additive interactions of heat wave, fine particulate matter, and ozone on cardiovascular mortality in a typical cold region of China: A time-stratified case-crossover study - Jinghao Wan; Mingzhao She; Hanhan Wang; Lixin Zheng; Xinyue Yu; Yuqian Song; Zhongran Wang; Min Li; Xu Han; Haibo Zhou; Zhifeng Xing; Xiao Bai; et al. (International Journal of Hygiene and Environmental Health, 2026)

Retraction notice to “Construction of a novel ursolic acid-based supramolecular gel for efficient removal of iodine from solution” [Environ. Res. 235 (2023) 116617] - Zhichun Shi; Xiuqi Huang; Yingnan Zhao; Jun Li; Yan Qing Tian; Piao Piao Zhang; Min Zhu; Ming Zhao (Environmental Research, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Direct observational evidence of the influence of residual-layer vertical transport on surface nitrate concentrations in a Northern China valley - Jiayun Li; Dantong Chen; Shengtong Lei; Min Zhang; Yiyang Gao; Pengfei Tian; Jinsen Shi; Xin Song; Yi Chang; Zirui Liu; Lei Zhang (Atmospheric Environment, 2026)

p-Block metal boosted oxygen electrocatalysis of Fe–N–C for alkaline seawater electrolyte-based zinc-air batteries - Yuxin Zhang; Yurong Liu; Xue Zhang; Meizhen Chen; Min Chen; Jing Li; Zhitong Wang; Yonghao Xiao; Xiaodong Shi; Zhenye Kang; Zhuoliang Jiang; Lutong Shan; et al. (Science Bulletin, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Metabolic footprint of microplastics and nanoplastics: From environmental exposure to metabolic diseases - Shuang Zhao; Huifang Guan; Zepeng Zhang; Jiarui Li; Chuanxi Tian; Xiao Sun; Mingda Han; Yue Zhang; Xiangyan Li; Min Li (NanoImpact, 2026)

Elucidating the role of ammonia doping in modulating combustion dynamics in ethane fuel-rich jet flames - Bipro Gain; Muhammad Bilal; Yun-Fan Wang; Ahmed E. Mansy; Muhammad Yousuf; Kai-Ru Jin; Du Wang; Boyang Su; Aqsa Liaqat; Mohammed Khalil; Zhi-Min Wang; Qingli Li; et al. (Fuel, 2026)

Real-time identification of natural ventilation pathways in high-rise housing using distributed PVA sensing and graph-based flow network model - Shilin Ming; Jianwei Li; Shengyu Liu; Hongxin Tian; Yuzhen Zhang; Chenyang Qin; Min Wang; Xiong Shen (Building and Environment, 2026)

DIRAS2 promotes the progression of oral leukoplakia via suppressing ferroptosis - Zitong Tian; Wenjing Li; Xing Li; Min Wang; Xiaofei Tang; Min Zhang (In Vitro Cellular & Developmental Biology - Animal, 2026)

Performance enhancement of CRISPR-Cas system based on improved guide RNA: a review - Xiaozhuang Zhang; Chenyan Tian; Min Wang; Huaiyu Jia; Xingrong Li; Guozhen Tian (Analytica Chimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Regional immunity in the respiratory tract: challenges and opportunities - Shuo Wang; Si Chen; Lianpan Dai; Fengqi Li; Hui Li; Kefang Liu; Xiangzhi Meng; Jian Wang; Hua Yue; Airu Zhu; Bin Cao; Ling Chen; et al. (Science Bulletin, 2026)

The ZxCNIH4-ZxHKT1;1 module responding to external NaCl orchestrates Na+ partitioning in a xerophyte - Jie Huang; Pei-Qin Li; Tian-Qiong Wang; Wan-Peng Bai; Hu-Jun Li; Jin Ke; Yuan-Zhou Pan; Suo-Min Wang (Plant Science, 2026)

Biological processes dominate the dynamic changes in the dissolved inorganic carbon ion equilibrium system of coastal wetlands under tidal influence - Yilin Wang; Tian Shi; Shuqi Xue; Junke Chen; Maomao Li; Min Xi (Marine Environmental Research, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Pre-molt cholesterol regulation of ecdysone receptor (EcR) signaling in the Y-organ contributes to dietary control of molting in Scylla paramamosain - Shichao Xie; Yao Deng; Yinqiu Tian; Zheng Tang; Tiantian Xu; Xiaoyue Li; Wenhao Zhan; Hongyu Peng; Yangguang Bao; Tingting Zhu; Wenli Zhao; Min Jin; et al. (Insect Biochemistry and Molecular Biology, 2026)

A refined model for rock damage during cyclic heating and cooling by coupling acoustic emission with P-wave analysis - Zhongyu Yu; Shiwei Shen; Wen Zhang; Miao Li; Min Zhang; Lupeng Tian; Guowen Hua (Engineering Geology, 2026)

Bioinspired ordered FeCo/biomass-derived carbon aerogels for broadband microwave absorption and multifunctional thermal-mechanical integration - Xiaoke Tian; Kun Wang; Huanhuan Li; Houjin Zhang; Xiaoman Xie; Min Yang; Yunjun Yan (Chemical Engineering Journal, 2026)

Structural characterization and antitumor activity via immune modulation of an α-glucan from Grifola frondosa - Hui-Xiang Tian; Qin-Zhao Ruan; Yi-Zhen Xie; Wei Chen; Chun Xiao; Wei Zhong; Yuan-Chao Liu; Shao-Dan Chen; Tian-Qiao Yong; Hui-Ping Hu; Xiang-Min Li; Qing-Ping Wu (Carbohydrate Polymers, 2026)

Regulation of Cadmium Uptake and Agronomic Traits in Rice by PEI-Induced Nanosilica Deposition - Xiao Tian; Yingming Feng; Xingyun Chen; Tao Wan; Chaozheng Huang; Xuewen Li; Sergey Shabala; Min Yu (Journal of Soil Science and Plant Nutrition, 2026)

Strontium and cesium accumulation in soil-rice system: Influencing factors and predictive modeling - Hong-Ling Chen; Bao-Min Yao; Zi-Yang Pan; Dong-Li Sun; Guang Yang; Tian-Ran Sun; Guo-Xin Sun (Soil Ecology Letters, 2026)

Dietary creatine supplementation promoted growth performance, muscle growth and protein deposition in red swamp crayfish (Procambarus clarkii) fed with all-plant-protein diets - Xinyuan Li; Changchun Song; Shouqi Xie; Min Wan; Yangyang Liu; Chenxi Wang; Guogen Su; Feng Huang; Juan Tian (Aquaculture, 2026)

Unveiling the resolution-induced variability in product carbon footprints: Evidence from multi-level electricity consumption data in footwear manufacturing - Bingqian Zhang; Chen Feng; Yacong Hu; Kun Yan; Fan Li; Tina Wu; Shawn Li; Paul Min; Luxus Li; Jinping Tian; Lyujun Chen (Resources, Conservation and Recycling, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

Controllable Preparation of Novel UiO-66-NH2/g-C3N5 Thin-Film Nanocomposite Nanofiltration Membranes with Efficient Photocatalytic Pollutant Removal and Anti-Fouling Ability - Jianghao Tian; Min Xiao; Shifeng Li; Ruiying Bu; Xin Yang; Hongling Zhang; Xiaoyang Chen (Water, Air, & Soil Pollution, 2026)

Genome-wide analysis of HSP70 family in Zygophyllum xanthoxylum and its heat stress response in Arabidopsis - Wan-Peng Bai; Tian-Qiong Wang; Qin Liu; Hu-Jun Li; Li Wei; Suo-Min Wang (Plant Cell Reports, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Pigment and transcriptome profiling of flesh yellowing during post-ripening of ‘Puyu’ kiwifruit - Tian Lan; Shihan Bao; Xinyi Li; Min Zhang; Wen Peng; Mukesh Kumar Awasthi; Xiangyu Sun; Tingting Ma (Postharvest Biology and Technology, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Evaluating the role of onboard carbon capture and storage system in remedial unit balancing under the IMO net-zero framework: Insights from GFI and 4E analysis - Yihang Zhou; Shuai Deng; Zhen Tian; Ke Li; Meng Lin; Li Zhao; Chunfeng Li; Xiaohan Zhao; Yijiang Tian; Wenjing Zhang; Min Shi (Journal of Cleaner Production, 2026)

Design of green multifunctional mesoporous nanosheets for trace biomarker detection, AI-enhanced pollutant discrimination, and synergistic catalytic degradation - Zamar Daka; Yuqi Zhang; Jieli Li; Liying Yao; Chenxi Luo; Meng Tian; Xi Xia; Guowen Qin; Rong Jiang; Min Song; Shunli Ji (Chemical Engineering Journal, 2026)

Unique characteristics of Candidatus Nitrosoglobus-driven acidic partial nitritation: critical review and potential applications - Tianyi Zhang; Yanyan Li; Shen Cui; Feng Tian; Min Ye; Yu-You Li (Bioresource Technology, 2026)

Identification of the methionine sulfoxide reductase (MSR) gene family in four Triticum species and functional analysis of TaMSRB5 involved in copper stress tolerance in Arabidopsis thaliana - Heng Chen; Luzhen Wang; Kexin Zhao; Shuai Yan; Yifei Chen; Lei Guo; Yinying Wu; Renmei Tian; Danping Li; Wenjia Zhang; Jianjun Liu; Haosheng Li; et al. (Plant Molecular Biology, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interface modification of membrane substrates: Mitigating microbial interfacial adhesion and augmenting adsorptive capacity for seawater uranium recovery - Piao Yi Jiang; Han Tang; Wang Kai Tong; Jiaxiang Liu; Kewei Liu; Wenxiang Tang; Jia Bing Liu; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2026)

Combined transcriptome and function analyses of peripheral blood white cells highlight the disease-resistant mechanism of CD79a/CD79b in Chinese tongue sole (Cynoglossus semilaevis) - Min Tian; Jinfeng Liu; Ruiqi Guo; Hua Li; Songlin Chen; Lei Wang (Fish & Shellfish Immunology, 2026)

Carboxymethyl cellulose-reinforced adhesive bio-patch for sealing wet tissue defects and bioelectronics - Jianpeng Zhang; Haofan Qu; Qiaoling Li; Gongwei Tian; Qingyang Wu; Min Zhang; Jianguo Li; Shengchang Lu; Dianpeng Qi; Hui Wu (Chemical Engineering Journal, 2026)

Plant-derived extracellular vesicles as a promising nanomedicine platform: engineering strategies and biomedical applications - Xin Zhang; Yifan Dong; Qing Tian; Yang Yang; Hongda Wang; Min Zhang; Yiuno Li; Xue Li; Qinhua Chen; Dean Guo; Wenzhi Yang (Chemical Engineering Journal, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Differences in Habitat Substrate Preference Selection Among Sexes and Populations of Leptobotia elongata - Lixiong Yu; Min Wang; Jiaxin Li; Fengyue Zhu; Yuliang Yuan; Huiwu Tian; Mingdian Liu; Weiwei Dong; Ji Yang; Senfan Ke; Chenyu Lin; Xinbin Duan (Fishes, 2026)
Cascade hydropower development in the upper Yangtze River has substantially altered riverine habitat conditions. However, quantitative information on fish substrate preferences remains limited. Based on field surveys, six representative substrate types were identified in the Yibin and Jiangjin reaches, and substrate selection patterns of Leptobotia elongata were quantified under controlled flume conditions. This study examined sex-specific and population-level differences in substrate preference. A total of 50 samples were analyzed using one-way ANOVA and the Kolmogorov–Smirnov test. The results are summarized as follows: (1) Substrates of 40–20 mm: Individual female L. elongata exhibited the longest residence time on the 40 mm substrate (1640 s), while individual males also spent the longest time on the 40 mm substrate (1549 s). Within this substrate range, males showed a preference only for the 40 mm substrate (PR = 739), whereas females preferred three substrate types, with the strongest preference for the 40 mm substrate (PR = 7543). (2) Substrates of 10–2.5 mm: Female individuals spent the longest time on the 10 mm substrate (1468 s), and male individuals likewise showed the longest residence time on the 10 mm substrate (1568 s). In this range, males did not show a significant preference for any substrate (PR = −907), whereas females preferred three substrate types, with the 2.5 mm substrate exhibiting the highest preference intensity (PR = 2059). (3) Population-level patterns for 40–20 mm substrates: The population spent the longest time on the 40 mm substrate (1799 s) and preferred three substrate types, among which the 20 mm substrate had the highest preference ratio relative to the other preferred substrates (PR = 4750). (4) Population-level patterns for 10–2.5 mm substrates: The longest residence time was observed on the 10 mm substrate (1762 s). The population preferred three substrate types, with the 10 mm substrate showing the highest preference ratio (PR = 5709). Overall, L. elongata showed a general tendency to prefer larger-sized substrates. This preference is likely associated with enhanced habitat complexity, improved foraging opportunities, and the formation of low-velocity refuges. Our results suggest that maintaining or restoring coarse substrate patches in regulated reaches may improve habitat suitability for L. elongata and potentially benefit other benthic fishes with similar ecological requirements.

RETRACTED: Asiatic acid reverses cisplatin resistance in A549/DDP cells by activating the P38 MAPK/Slug pathway - Min Yu; Qian Zhang; Wenli Shang; Shenghong Wei; Hongxia Wen; Shufen Huo; Xiang Li; Xuan Li; Heng Zhang; Yingxuan Tian (Tissue and Cell, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

Hydrogenophaga-bioaugmented microalgal-bacterial granular sludge for efficient treatment of chloramphenicol-containing wastewater - Shengjie Xiang; Yang Bai; Min Yu; Hassimi Abu Hasan; Yuting Shi; Can Tong; Yuan Tian; Anjie Li; Bin Ji (Journal of Environmental Chemical Engineering, 2026)

Deciphering the microbial complexity of Chinese traditional sourdough through integrated learning - Yan Liu; Jinyu Wang; Shiwei Zhou; Feijiang Li; Honghong Cheng; Zheqing Zhu; Jiale Wang; Aowen Liu; Ting Lu; Yujuan Yu; Senmiao Tian; Min Zhang; et al. (Food Research International, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Graphite Carbon Supported Single-Atom Iron Catalyst Activates Persulfate for Phenol Degradation: Radical and Non-Radical Synergistic Mechanism - Shifeng Li; Mengran Chu; Yu Tian; Juan Yang; Shuhua Yao; Min Xiao (Water, Air, & Soil Pollution, 2026)

Assessing the response of terrestrial water storage to climate warming in China by coupling CMIP6 multi-model ensembles, hydrological model, and machine learning algorithms - Xiaoyan Cao; Jiali Ju; Chuanhao Wu; Pat J.-F. Yeh; Min Shi; Ashraf Dewan; Yongze Song; Xueyuan Zhang; Tian Yao; Yufei Jiao; Qiongfang Li; Shanshui Yuan; et al. (Climatic Change, 2026)

Molecular mechanisms of cold stress-induced energy stress, cholesterol metabolic disorders, and apoptosis in Pangasianodon hypophthalmus - Dongjie Wang; Min Li; Min Liao; Yao Tian; Qing Wu; Shaolin Xie; Wei Luo; Jixing Zou; Jun Shi; Zongjun Du (Aquaculture, 2026)

Surface Co-passivation for 1.7 eV wide-bandgap perovskite solar cells with minimal voltage loss to achieve over 23% efficiency - Mengjin Zhang; Yang Guo; Min Wang; Zequn Ma; Xiaogang Yang; Linxing Meng; Hao Lu; Wei Tian; Liang Li (Science Bulletin, 2026)

Avermectin and cyclobutrifluram cause oxidative stress and energy metabolic disorders of Caenorhabditis elegans - Jingyu Tian; Herui Zhang; Caihong Yu; Ronghua Lin; Liang Liu; Min Li; Yue Yin (Pesticide Biochemistry and Physiology, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Spatio-temporal distribution and production-consumption dynamics of nitric oxide in coastal waters off Qingdao, China - Yun-Fei Li; Ye Tian; Hui-Min Jian; Chun-Ying Liu; Tian-Tian Ge; Pei-Feng Li; Gui-Peng Yang (Marine Environmental Research, 2026)

Targeted control of beef spoilage: Integrating slaughter-source tracking with packaging-temperature hurdles for precision preservation - Jiarui Li; Dequan Zhang; Ming Tian; Chengjun Min; Debao Wang; Xin Li; Xiaotong Sun; Yanan Tang; Yuxia Qi; Chengli Hou (Food Research International, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Enhanced efficacy of anaerobic membrane bioreactor (AnMBR) for treating pharmaceutical wastewater with abundant protein particles - Ye Tian; Hui Cheng; Yupeng He; Haodi Feng; Wen Shi; Jie Sun; Yuyou Li; Yu Zhang; Min Yang; Zhe Tian (Chemical Engineering Journal, 2026)

Corrigendum to “starch and castor oil mutually modified, cross-linked polyurethane for improving the controlled release of urea” [carbohydrate polymers 251 (2021) 117060] - Hongyu Tian; Zeli Li; Panfang Lu; Yong Wang; Cong Jia; Huaili Wang; Zhiguang Liu; Min Zhang (Carbohydrate Polymers, 2026)

Ginsenosides secreted by Panax notoginseng promotes the growth and pathogenicity of Fusarium oxysporum through enhancing antioxidant capacity - Lifen Luo; Rong Lu; Rong Yin; Guangxiang Tian; Yiwen Li; Guixiang Li; Hongwei Zhu; Jianqiang Miao; Jianjun Hao; Xili Liu; Shusheng Zhu; Min Yang (Plant and Soil, 2026)

Spatial variation of rainfall for landslide early warning: an examination from Majiajing watershed in Yunnan, China - Jing-Kun Bao; Kun Wang; Chuan-Bing Zhu; Ze Li; Ze-Min Xu; Yun-Fei Zhang; Lin Tian; Yang Yang; Jun-Yao Luo; Tai-Qiang Yang (Natural Hazards, 2026)

Field and laboratory investigations of the fluid in fully developed debris flows - Xiao Su; Ze-Min Xu; Yi-Xi Wen; Bin Li; Jing-Kai Meng; Lin Tian; Zi-Ming Ye; Gui-E Shi (Bulletin of Engineering Geology and the Environment, 2026)

Gold nanorod-mediated multicolor biosensor for visual detection of Streptococcus agalactiae during pregnancy in actual clinical samples - Xiaozhuang Zhang; Yubin Zhang; Fukang Li; Huaiyu Jia; Min Wang; Guozhen Tian (Analytica Chimica Acta, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Distinct mechanisms of soil organic carbon formation in natural and legume-based grasslands on the Loess Plateau, China - Zi-Qiang Yuan; Chao Fang; Tian Ma; Jiu-Ying Pei; Xin Song; Guang-Qian Yao; Jordi Sardans; Josep Penuelas; Xiang-Wen Fang; Feng-Min Li (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Ethyl-Nα-lauroyl-L-arginate hydrochloride treatment inhibited the in vitro growth of Penicillium expansum and enhanced disease resistance in pear fruit - Tian Gao; Yajun Wang; Shuang Min; Huixin Fang; Jiahui Cai; Canying Li; Yonghong Ge (Postharvest Biology and Technology, 2025)

Regulation of terephthalic acid metabolism drives the enhancement of PET degradation in Ideonella sakaiensis - Xiao-Min Zhao; Yang Li; Tian-Tian Wang; Qing-Song Huang; Chu-Qi Feng; Jing Wu; Zheng-Fei Yan; Sheng Chen (Journal of Hazardous Materials, 2025)

Characteristics of carbon sequestration in coastal saline-alkali soils of the Yellow River Delta and their response to crop planting patterns - Mengyan Liu; Xinhua Li; Maomao Li; Yilin Wang; Tian Shi; Min Xi (Journal of Environmental Management, 2025)

Mixed gas nanobubbles promote microbial CO2 fixation: Universal verification, mechanism, and application - Jia Wang; Piao Yi Jiang; Jia Bing Liu; Han Tang; Wang Kai Tong; Jia Jie Zou; Mei Ru Yue; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2025)

Rapid change in structural stability of tidal flats in response to large-scale eradication of Spartina alterniflora: evidence from dense time-series PlanetScope satellite imagery - Jiaru Yang; Liyue Cui; Zhaojun Zhuo; Jinyan Tian; Peng Li; Yukui Min; Yinghai Ke (Journal of Environmental Management, 2025)

Leaching mechanism of Ca and Mg from converter steel slag in seawater - Kai Zhang; Ya-jun Wang; Jun-guo Li; Zi-hao Xu; Yi-tong Wang; Tian-ji Liu; Ai-min Gao (Journal of Environmental Chemical Engineering, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Synergistic enhancement of nitrate selectivity in electrodialysis under high salinity via membrane hydrophobic modification and mass transfer optimization - Ling Feng; Hanfei Li; Feiyu He; Binghui Tian; Min Yang (Desalination, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Synergistic engineering of P-doping and oxygen vacancies combined with LSPR effect to enhance hydrogen evolution performance of P-MoO2-x@C - Jiaqi Liang; Qinfen Tian; Xingyu Chen; Xin Li; Guofa Dong; Yali Xie; Ziyu Lian; Yibin Wu; Juan Lu; Min Niu; Jiandong Zhuang (Chemical Engineering Journal, 2025)

Gastrodin inhibits hexokinase-2 mediated glycolysis to rescue rotenone-damaged PC12 cells - Min Chen; Jiaming Tian; Buyun Jia; Meng Wang; Anqi Han; Jiming Zhu; Shasha Tian; Xiaoming Gao; Baikun Li; Qinglin Li; Shanshan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The role of canopy family proteins: biological mechanism and disease function - Xue Li; Min-Yue Yin; Shu-Tian Zhang; Si-An Xie (Molecular Biology Reports, 2025)

Study on the remediation of uranium contaminated water by indigenous bacteria in tailing pond and the mechanism of mineralization and precipitation - Jinxiang Deng; Mengjie Li; Lingling Wu; Zhijun Zhang; Huaimiao Zheng; Lin Hu; Yakun Tian; Min Wang (Process Safety and Environmental Protection, 2025)

Mortierella alpina bioinoculant potentiates native microbiota for soil borne disease suppression in Panax notoginseng cultivation - Yingpin Liu; Yan Hu; Yue Li; Guangxiang Tian; Lifen Luo; Sihan Zhao; Chen Ye; Xinyue Mei; Weiping Deng; Shusheng Zhu; Min Yang (Pesticide Biochemistry and Physiology, 2025)

Regulating dispersion of OEO Pickering emulsion to construct smart antibacterial nanocellulose packaging films contained microcapsule - Qing Meng; Tao Wang; Siting Li; Hangyu Xie; Honghong Tian; Min Wu; Xueping Song (Food Chemistry, 2025)

A novel strategy based on mouse organoid biosensor for detecting umami substances and their synergistic effect - Minbo Li; Min Fan; Baifeng Fu; Zhihui Chang; Junjie Yi; Yingqi Xie; Wenwen Ren; Yu Tian; Qiyue Zhao; Shuzhen Cheng; Xianbing Xu; Ming Du (Food Chemistry, 2025)

The small GTP-binding Ras-like protein DIRAS2 promotes cell proliferation in oral leukoplakia via the RAF/MEK/MAPK pathway - Jing Li; Zitong Tian; Wenjing Li; Min Wang; Xiaofei Tang; Min Zhang (Tissue and Cell, 2025)

Unraveling the influence of naphthalene on methane production from anaerobic digestion of waste activated sludge - Yanxin Wu; Junyi Li; Min Lu; Ke Tian; Chao Wu; Manyu Wang; Zifan Guo (Science of The Total Environment, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Enhancing soil carbon sequestration capacity: Synergistic effect of low-release biochar and autotrophic microbial agents over one year - Han Tang; Jiajun Hu; Yundong Liu; Bu Li; Jia Wang; Wang Kai Tong; Mei Ru Yue; Jia Jie Zou; Min-tian Gao; Saiwei Zhang; Nan Liu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Molecular insights into sodium alginate selective flotation separation of bastnaesite from calcite and fluorite - Min Liu; Jia Tian; Longhua Xu; Xin Wu; Guohuan Li; Zhiyuan Wang; Kaiqian Shu; Kai Xue; Yi Luo; Yue Cao; Donghui Wang; Zhoujie Wang (Journal of Environmental Chemical Engineering, 2025)

Emission fluxes of nitrous acid (HONO) from livestock and poultry wastes - Wenjin Zhang; Pengfei Liu; Min Song; Xuran Li; Xiaoxi Zhao; Yifei Song; Di Tian; Chenglong Zhang; Yuanyuan Zhang; Yangang Ren; Chengtang Liu; Junfeng Liu; et al. (Journal of Environmental Sciences, 2025)

Multiobjective optimization of cyclodextrin-enhanced extraction of caffeoylquinic acids and trigonelline from Coffea arabica pulp via homogenate–ultrasound synergy and hybrid modeling - Zhan Shen; Hao Tian; Yang Yang; Min Li; Zhen Wang; Lei Yang; Jialei Li (Innovative Food Science & Emerging Technologies, 2025)

Investigating the effect of MAG/(NaPO3)x on the physicochemical and structural properties of rice starch-protein rice and improving the mechanism in each zone during the extrusion process - Li-shuang Wang; Jia-Sun; Jin-hui Jia; Jin-jie Huo; Yu-min Duan; Na-Wang; Xiao-shuai Yu; Zhi-gang Xiao; Ying Wang; Xiao-ling Tian (Food Structure, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Curved Fe-N4 sites endows effective oxygen reduction reaction in acid medium - Yalin Liu; Gai Li; Min Chen; Yurong Liu; Tianyu Qiu; Xingqi Han; Jing Li; Ruisong Li; Xiaodong Shi; Zhenye Kang; Qinhe Pan; Xinlong Tian; et al. (Chemical Engineering Journal, 2025)

Targeted air supply to the working area of a tall plant based on the principle of fluid topology optimization - Hongchen Li; Dongzheng Wang; Min Zhou; Yonghong Jia; Yan Tian; Yang Xuan; Yafan Jin; Ran Gao (Building and Environment, 2025)

MAO-A inhibition alleviates sepsis-driven lung injury via Nrf2/HO-1 pathway activation and suppression of pyroptosis - Min Li; Hu Li; Liming Gong; Xinmin Chen; Jincan Dai; Jirong Tian; Xiaochuan Yin; Qinghe Yu (Journal of Molecular Histology, 2025)

Highly water-soluble AIEgen for α-amylase activity ultrasensitive detection and ovarian cancer rapid theranostic - Xing Wang; Yuanhang Li; Penglin Wu; Li Yang; Tian Min; Shengnan Yao; Huilin Dong; Zhengjian Qi (Analytica Chimica Acta, 2025)

ORMCKB: A Knowledge Database for Personalized Medicine in Deciphering the Oral Microbiome-Disease Axis - Yutao Wu; Yi Zhou; Wenjing Shi; Siyu Zhou; Min Jiang; Ke Shen; Xingyun Liu; Xiaoyu Li; Jiao Wang; Chi Zhang; Bairong Shen; Weidong Tian (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Modifying polysaccharides to realized advanced function of novel food packaging materials - Hangyu Xie; Siting Li; Honghong Tian; Yi'er Lou; Yuanxin Ouyang; Min Wu; Xueping Song (Trends in Food Science & Technology, 2025)

Spectral characteristics of organic matter from algae and its complexation with copper: a case study of Ulva prolifera - Tian-Zi Zhang; Li-Min Zhou; Yu-Yuan Wang; Lu Han; Xiao-Yan Cao; Gui-Peng Yang (Marine Environmental Research, 2025)

ABA is involved in OsDSR3-mediated regulation of alkali tolerance in rice - Xuping Lu; Weifang Min; Yangmengfei She; Tinglu Liao; Donghao Xiao; Lei Tian; Peifu Li; Chengke Luo (Journal of Plant Physiology, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

Applying stacked machine learning models to guide electrochemical oxidation of antibiotics: Key parameter identification and process optimization insights - Shichang Jia; Min Deng; Yue Mu; Jiahang Li; Xiaosong Tian; Qing Xie; Jinzhong Zhang (Journal of Environmental Management, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

Exploring the masking of berberine bitterness by natural polysaccharides based on a “net-hook” dual-effect mechanism - Min Qiu; Jiaxin Li; Huijuan Xie; Jiamin Feng; Qi Huang; Yin Tian; Haozhou Huang; Li Han; Dingkun Zhang (Carbohydrate Polymers, 2025)

Groundwater-mediated U–Th–Pb differential migration in monazites during hydrochemical weathering - Hao-Xiang Zhang; Shao-Yong Jiang; Wen-Tian Li; Wei Zhang; Hui-Min Su (Chemical Geology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Bioactive terpenoids and sterols from the fruiting bodies of Fomitopsis pinicola - Huan Yu; Qian Chen; Tian-Chi Xu; Yue Wang; Wen-Feng Xu; Min Li; Xu Zhang; Chuan Zhao; Dong-Li Zhang; Peng-Fei Jin; Shao-Yong Li; Sheng-An Tang (Phytochemistry, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Environmental high-risk efflux pumps mediate concurrent enhancement of resistance and virulence in reclaimed water from urban wastewater treatment plants - Shanqi Shen; Zhong He; Siya Zhao; Zezhang Zhu; Xinyi Wang; Yechao Tian; Yuze Han; Min Hu; Chang Lu; Aimin Li (Journal of Hazardous Materials, 2025)

Acclimatization of salt-tolerant bacteria in a pilot-scale biological treatment system for actual high-salinity wastewater from a chemical industrial park - Yifan Feng; Chunlei Yang; Jun Li; Xinchun Ding; Ruize Xia; Min Hu; Yechao Tian; Yang Pan; Quanxing Zhang; Aimin Li (Journal of Environmental Chemical Engineering, 2025)

Optimization of wheat straw liquefaction conditions and phy-chemical characterization of liquefied products - Zhan Ding; Linyu An; Min Yang; Hangbo Liu; Chenxi Tian; Fengkai Liu; Peilong Li (Biomass and Bioenergy, 2025)

Inter-model comparison of the DRI-2001 and DRI-2015 for carbonaceous aerosol analysis in PM2.5: Method development and application in Chongqing - Chao Peng; Chongzhi Zhai; Yang Chen; Mi Tian; Ying Xiang; Tianyu Zhai; Weikai Fang; Xin Long; Xiaocheng Wang; Mulan Chen; Yunqing Cao; Min Du; et al. (Atmospheric Pollution Research, 2025)

Immunomodulatory Effects of Lactiplantibacillus plantarum Strain RW1 During Salmonella Infection in Murine Intestinal Epithelial Cells and Dextran Sulfate Sodium-Induced Murine Colitis - Guangzhi Zhang; Abdul Raheem; Xiaofeng Xu; Xuezheng Fan; Jianwei Zhang; Tong Qin; Li Jia; Min Yue; Weifang Yang; Liang Wang; Mingyan Wang; Yajie Yin; et al. (Probiotics and Antimicrobial Proteins, 2025)

New Insights Into the Phylogeny and Biogeography of Goji Berries ( Lycium , Solanaceae) Inferred From Plastid Data - Gulbar Yisilam; Kenneth M. Cameron; Zhi‐Yong Zhang; En‐Ting Zheng; Chuan‐Ning Li; Zhen‐Zhou Chu; Ying Su; Jia‐Lei Li; Yu‐Wei Wang; Jin Li; Pan Li; Xin‐Min Tian (Journal of Biogeography, 2025)
Aim Lycium L. (Solanaceae), which is known for producing goji berries, is an important plant with both medicinal and edible uses. This genus is globally distributed in temperate and subtropical regions. However, a comprehensive phylogeny and evolutionary history of this plant group is lacking so far. This study was executed to produce novel insights into the phylogenetic relationships and evolutionary history of this small but economically important genus. Location North America, South America, Hawaii, Africa and Eurasia. Taxon Lycium L. (Solanaceae). Methods We established a phylogenetic framework for Lycium based on complete plastome sequences and data from 80 protein‐coding genes across 43 Lycium species using maximum likelihood and Bayesian inference methods. Furthermore, 14 species from the Solanaceae family were used as outgroups. Additionally, two Solanoideae fossils and one secondary calibration point were used to estimate divergence times and reveal the biographical history of these plants through ancestral area reconstruction. Results Our analysis revealed that six North American Lycium species were strongly supported as monophyletic with high support and were sister clades to the remainder of the genus. The remaining species from North America, South America and the Hawaiian Islands shared a common ancestor, whereas all species from Africa, Saharo‐Arabia and Eurasia formed a distinct clade. Our results indicated that Lycium originated in North America during the Late Oligocene and then dispersed to Hawaii and South America, from there to Africa, and then further to Saharo‐Arabia, with a more recent dispersal to Eurasia. Main Conclusions Our plastid genome data confirmed that Lycium originated in North America and identified long‐distance dispersal as the key to its global distribution. Genomic insights facilitate species identification and contribute to conservation efforts.

Steel frame joints with multistage performance for collaboratively resisting earthquakes - Jian-peng Wei; Han Tian; Dong-hua Wang; Li-min Tian (Soil Dynamics and Earthquake Engineering, 2025)

Source of dietary iron and zinc affects meat quality by altering muscular fatty acid profile, flavor substances, and metabolomics in finishing pigs - Zhimei Tian; Miao Yu; Yiyan Cui; Dun Deng; Min Song; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Meat Science, 2025)

Degradation-Resistant Biochar Improves Soil Organic Carbon Storage: Promoting Autotrophic Metabolism & Increasing Refractory Organic Carbon - Han Tang; Jiajun Hu; Bu Li; Yundong Liu; Wang Kai Tong; Mei Ru Yue; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jixiang Li (Bioresource Technology, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Probing the mechanism of prolonged ozone pollution in arid and semi-arid urban areas - Xin Song; Pengfei Tian; Zeren Yu; Xiaoxue Liu; Tao Wang; Min Zhang; Jiayun Li; Xianjie Cao; Jiening Liang; Yan Ren; Min Chen; Lei Zhang (Urban Climate, 2025)

Surface and interface modification of biochar based on thermal nanobubble water - Mei Ru Yue; Jia Bing Liu; Piao Yi Jiang; Wang Kai Tong; Han Tang; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Sustainable nanofiber films based on polylactic acid/modified cellulose nanocrystals containing various types of polyphenols, exhibiting antioxidant activity and high stability - Chaoqiao Zhu; Qingfeng Yang; Ming Tian; Wei Yang; Chengjun Min; Simin Fan; Debao Wang; Xin Li; Dequan Zhang; Chengli Hou (Food Chemistry, 2025)

Synergistic effects of bimetallic Co, Cu activity sites and heteroatom-doped carbon nanotube-entangled phosphide for high capacity lithium storage - Hanlin Shen; Zhuo Li; Min Dai; Yunan Tian; Zhaoshun Liu; Zhonghao Zhou; Zhi Li; Xianwei Hu (Chemical Engineering Journal, 2025)

Liquid-phase exfoliation of 2D transition metal dichalcogenide nanosheets in water - Weiqian Tian; Min-A Kang; Jyoti Shakya; Qingchen Li; Xiaoyan Sui; Mengyu Liu; Huanlei Wang; Mahiar Max Hamedi (Chemical Engineering Journal, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Atomized fumigation with basil essential oil regulated reactive oxygen metabolism and respiratory metabolism to maintain storage quality of blueberry fruit - Yajun Wang; Shuang Min; Tian Gao; Canying Li; Yonghong Ge (Postharvest Biology and Technology, 2025)

Spatial-temporal distribution and emission of urban scale air pollutants in Hefei based on Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Min Qin; Jin Xu; Zhaokun Hu; Xin Tian; Feng Hu; Yinsheng Lv; Jiangyi Zheng; Youtao Li (Journal of Environmental Sciences, 2025)

A comprehensive evaluation of appearance stability during rice storage based on analytic hierarchy process - Jinyu Tian; Mingjin Jiang; Guangmei Ji; Jiafeng Zhang; Danqiu Luo; Fang Zhang; Lijiang Li; Min Li (Journal of Cereal Science, 2025)

Synergistic effects of matrix metalloproteinases on the degradation of collagen in abalone (Haliotis discus hannai) - Yu-Lei Chen; Le-Le Su; Hua Liu; Tian-Bo Zhang; Guiling Li; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Min-Jie Cao (Food Chemistry, 2025)

Unravelling the fouling behavior of cation exchange membrane (CEM) by waste salt containing decyltrimethylammonium chloride during membrane electrolysis - Ling Feng; Binghui Tian; Li Chen; Min Yang (Environmental Research, 2025)

Bonding of wood with high strength and excellent water resistant cellulose colloidal adhesives - Yuyan Jiang; Tian Ju; Liangxian Liu; Haiyu Li; Yue Zhang; Na Wang; Zetan Lu; Ming Wei; Dexiu Min; Yanjun Xie; Jian Li; Yonggui Wang; et al. (Chemical Engineering Journal, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Simultaneously improve autotrophic denitrification and membrane fouling mitigation under low sludge concentration in sulfur-fed membrane bioreactor - Shanshan Gao; Ting Li; Mingyue Geng; Binghan Xie; Junliang Dong; Min Gao; Jiayu Tian (Journal of Environmental Chemical Engineering, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Corrigendum to “Atmospheric microplastic input into wetlands: Spatiotemporal patterns, drivers, and unique ecological impacts” [Water Research, 268 (2025): 122601] - Libo Xu; Xudong Tian; Xinyi Bai; Kang Li; Guangbao Zhang; Mengjun Zhang; Matthias C. Rillig; Yi Huang; Min Hu (Water Research, 2025)

Phenyllactic acid primed reactive oxygen species metabolism and phenylpropanoid pathway to induce resistance against Alternaria alternata in Malus domestica - Shuang Min; Jiaxin Liu; Canying Li; Tian Gao; Yajun Wang; Yonghong Ge (Physiological and Molecular Plant Pathology, 2025)

Comprehensive analysis of transplacental transfer of environmental pollutants detected in paired maternal and cord serums - Ke-Yu Yuan; Yao-Hua Gu; Yi-Hao Pei; Si-Yu Yu; Tian-Zhou Li; Tian Feng; Yu Liu; Jianbo Tian; Xiaoping Miao; Jun Xiong; Min Hu; Bi-Feng Yuan (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Bifunctional nanobody facilitates a colorimetric and fluorescent dual-mode immunoassay of Staphylococcal enterotoxin A - Yao Zhang; Di Liu; Yudong Tian; Min Li; Yuhuan Li; Ting Zhou; Qin Zhao; Min Zhang; Ying Yu; Hu Pan; Yanna Dai; Zhuoma Dawa; et al. (Food Chemistry, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Exosomal miRNA reprogramming in pyroptotic macrophage drives silica-induced fibroblast-to-myofibroblast transition and pulmonary fibrosis - Lin Zhang; Jiaqi Tian; Ning Li; Yongheng Wang; Yulan Jin; Hongying Bian; Min Xiong; Zitong Zhang; Jiahua Meng; Zhengpu Han; Shuyin Duan (Journal of Hazardous Materials, 2025)

Fabrication of PBS/PLA/Fibroin-Agarose nerve guidance conduit with sandwich compression resistant wall structure for repairment of 10 mm-sciatic nerve defect - Wen Zhang; Meng-Fei Hao; Hao Peng; Dong-Yi Wei; Jing-Jing Yao; Tian Guo; Li-Min Yang; Hua-Jie Wang (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Optimization and application of induction technology of double haploid in pumpkin (Cucurbita moschata D.) - Ziyang Min; Qi Wu; Jiajia Li; Shuitian Chen; Yongqi Li; Xiaoxia Han; Tian Zou; Xinjun Hu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Atmospheric microplastic input into wetlands: Spatiotemporal patterns, drivers, and unique ecological impacts - Libo Xu; Xudong Tian; Xinyi Bai; Kang Li; Guangbao Zhang; Mengjun Zhang; Matthias C. Rillig; Yi Huang; Min Hu (Water Research, 2025)

pH-dependent cadmium binding to hemoglobin: Implications for human excretion - Min Yuan; Qiying Nong; Hua Guo; Yu Li; Haozhong Tian; Jiaao Zhang; Lihong Liu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2025)

Structural characterization and proteomic profiling of oviposition secretions across three rice planthopper species - Jia-Bao Lu; Peng-Peng Ren; Ying Tian; Yan-Yan Yang; Qing-Kai Feng; Xiao-Ya Zhang; Fang He; Hai-Jian Huang; Jian-Ping Chen; Jun-Min Li; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2025)

Inhibitory effects of phytic acid on the in vitro and in vivo growth of Trichothecium roseum in apple fruit and the underlying mechanisms involved in its action - Yajun Wang; Xiaonan Ji; Shuang Min; Tian Gao; Canying Li; Yonghong Ge (Food Chemistry, 2025)

Glycated walnut meal peptide‑calcium chelates (COS-MMGGED-Ca): Preparation, characterization, and calcium absorption-promoting - Zilin Wang; Litong Liu; Haifen Jiang; Lingfei Li; Min Yang; Jiahe Dai; Liang Tao; Jun Sheng; Yang Tian (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

An improved rock damage model from a cyclic temperature – triaxial loading experiment for compressed air energy storage caverns - Zhongyu Yu; Shiwei Shen; Miao Li; Min Zhang; Lupeng Tian; Guowen Hua (Engineering Geology, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

A Review of Iron-Based Catalysts for Persulfate Activation to Remove PFAS in Water: Catalytic Effects of Various Iron Species, Influencing Factors and Reaction Pathways - Mengjie Zhang; YiYi Li; Xia Tian; Liang Dai; Gang Wang; Zhenle Lei; Gui Ma; Qianlin Zuo; Min Li; Mengmeng Zhao; Jun Ren (Water, Air, & Soil Pollution, 2025)

Crosstalk Between the Nervous System and Colorectal Cancer - Xi Li; Chunshui Ye; Min Wang; Patrick Kwan; Xin Tian; Yanke Zhang (Neuroscience Bulletin, 2025)

Dietary Iodine Can Effectively Alleviate the Adverse Effects of Fermented Rapeseed Meal on the Growth, Liver Health, and Antioxidant Capacity of Tilapia (GIFT, Oreochromis niloticus) - Di Peng; Ya-Xue Li; Li-Xue Dong; Ke Cheng; Hua Wen; Juan Tian; Jian-Min Zhang; Yang-Yang Liu; Wei-Hua Gao; Yong Min; Ming-Dian Liu; Ming Jiang (Fishes, 2024)
An 8-week feeding trial was conducted to evaluate the effects of dietary fermented rapeseed meal (FRM), potassium iodide, and their interactions on growth performance, approximate composition, and antioxidant capacity in tilapia, Oreochromis niloticus (initial body weight: 3.50 ± 0.15 g). Six isonitrogenous and isolipidic diets from a 2 × 3 factorial design were formulated with two levels of FRM (25.8 and 51.6%) and three levels of potassium iodide (0, 6, and 12 mg/kg), respectively. The results indicated that dietary levels of FRM and iodine had no significant influence on the SR of tilapia but exerted significant effects on weight gain (WG), specific growth rate (SGR), feed intake (FI), hepatosomatic index, and viscerosomatic index. The WG, SGR, and FI of tilapia in the 51.6% FRM groups were significantly lower than those in other groups (p

China-specific unit process dataset for lithium-ion batteries - Xi Tian; Haoyu Li; Fei Peng; Yibing Wang; Kaiwen Xiong; Rongjian Zhao; Min Liao; Yaodan Zhang; Bingqian Zhang; Jinliang Xie; Huimin Chang; Xin Sun; et al. (Resources, Conservation and Recycling, 2024)

Model the evolutionary pattern of N species and pool size in groundwater continuum by utilizing measured source and sink rates of nitrate and ammonium - Li-Li Han; Lianghao Ge; Ehui Tan; Wenbin Zou; Li Tian; Ping Li; Min Nina Xu; Shuh-Ji Kao (Journal of Hazardous Materials, 2024)

Eco-friendly, stable, and high-performance biochar prepared by a twice-modification scheme: Saccharification of raw materials & thermal air oxidation of biochar - Yundong Liu; Bu Li; Wang Kai Tong; Han Tang; Zhaoli Ping; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2024)

Statistical studies of the characteristics and key influencing factors of sediment changes in the upper Yangtze River over the past 60 years - Lvze Duan; Yiman Tian; Shuanghu Zhang; Xingbo Wang; Chong Li; Min Chen (Geomorphology, 2024)

DHMBA, a molecule from Pacific Oyster (Crassostrea gigas) alleviates AD pathology by inhibiting the ubiquination of Nrf2 - Yi-Fan Li; Min-Yu Chen; Yu Chen; Jian-Feng Chen; Xuan Zhang; Wen-Sheng Cai; Jing Tian; Ziniu Yu; Yang Zhang (Food Bioscience, 2024)

Response processes to water quality changes driven by the dynamic regeneration of the surface microlayer film in slow-flowing freshwater bodies - Yuankun Yang; Lunzhen Li; Yu He; Tian Ma; Juncheng Zheng; Maosheng Wang; Weiguo Tu; Min Fan; Shu Chen (Environmental Pollution, 2024)

Effects of cellulase treatment on properties of lignocellulose-based biochar - Bu Li; Yundong Liu; Wang Kai Tong; Jun Bo Zhang; Han Tang; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Bioresource Technology, 2024)

Genotype–phenotype correlation study of structural abnormalities in a fetal brain caused by a novel KDM4B variant - Xuliang Zhao; Xu Li; Min Yu; Jian-an Jia; Ruixia Tian; Fuxi Zhu (Molecular Biology Reports, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Comprehensive evaluation and screening of saline–alkali tolerant Japonica rice accessions during the whole growth stage - Chengbin Qiao; Kairong Duan; Jiawei Song; Zilan Jiao; Min Chen; Yue Dong; Jingwen Wang; Shuaiguo Ma; Na Wang; Chengke Luo; Peifu Li; Lei Tian (Euphytica, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Enhancing thermoelectric performance via synergistic regulation of band structure and microstructure in Cu-doped WS2 polycrystalline films - Nan Xin; Yifei Li; Guihua Tang; Tian Lan; Jimin Xu; Xin Zhao; Min Zhang; Yinan Nie; Hao Shen (Chemical Engineering Journal, 2024)

Engineering highly efficient root-inspired microporous layer for high-performance fuel cells - Qinglin Wen; Can He; Fandi Ning; Min Shen; Yiyang Liu; Zhi Chai; Xi Cheng; Xiong Dan; Siyi Zou; Wei Li; Lei He; Bin Tian; et al. (Chemical Engineering Journal, 2024)

Decoding the biochemical dialogue: metabolomic insights into soybean defense strategies against diverse pathogens - Min Qiu; Mengjun Tian; Yaru Sun; Huaibo Li; Wenwen Huang; Haibing Ouyang; Shaoyan Lin; Chen Zhang; Ming Wang; Yuanchao Wang (Science China Life Sciences, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Typical emerging contaminants in sewage treatment plant effluent, and related watersheds in the Pearl River Basin: Ecological risks and source identification - Xiaohui Zhu; Siyan Liu; Xiaofeng Gao; Yilu Gu; Ying Yu; Min Li; Xiaowen Chen; Mengqi Fan; Yujie Jia; Liping Tian; Mingdeng Xiang; Yunjiang Yu (Journal of Hazardous Materials, 2024)

Modification of Yarrowia lipolytica via metabolic engineering for effective remediation of heavy metals from wastewater - Kaixin Yang; Guowei Zhao; Huanhuan Li; Xiaoke Tian; Li Xu; Jinyong Yan; Xiaoman Xie; Yunjun Yan; Min Yang (Journal of Hazardous Materials, 2024)

Changes of intestinal barrier in the process of intestinal inflammation induced by Aeromonas hydrophila in snakehead (Channa argus) - Xue-qin Wu; Xiu-mei Chen; Yi-yu Pan; Chuang Sun; Jia-xin Tian; Ai-dong Qian; Xiao-tian Niu; Yi-di Kong; Min Li; Gui-qin Wang (Fish & Shellfish Immunology, 2024)

Combining metabolomics and transcriptomics to analyze key response metabolites and molecular mechanisms of Aspergillus fumigatus under cadmium stress - Qinghua Tian; Junjun Wang; Shiyu Shao; Hao Zhou; Jue Kang; Xinyi Yu; Min Huang; Guanzhou Qiu; Li Shen (Environmental Pollution, 2024)

Sulfur-driven microbial fuel cells denitrification system for targeted treatment of nitrate-containing groundwater: Performance and mechanism - Yue Li; Han-Min Zhang; Yu Tian (Chemical Engineering Journal, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Experimental and numerical study on seismic performance of assembled platform canopy with mortise-tenon joints - Yu-zhen Chang; Jiu-yi Kuang; Chong Bai; Yu-jun Cai; Dan-ning Wang; Yuan Wang; Li-min Tian (Soil Dynamics and Earthquake Engineering, 2024)

Enhancement the wastewater treatment performance of multistage living machine by underwater lamp - Ruihuan Chen; Tian Li; Guiying Huang; Xianle Jia; Zhan Jin; Xiangyong Zheng; Min Zhao (Journal of Environmental Management, 2024)

Activated carbon/persulfate-driven in-situ remediation of naphthalene-polluted groundwater: Insights into active sites, passivation-activation mechanisms and practical applications - Chaomeng Dai; Jun Bo Zhang; Jia Jie Zou; Jiajun Hu; Min-tian Gao; Zhi Li; Yucang Liang; Lang Zhou (Journal of Environmental Chemical Engineering, 2024)

Antibacterial polyamide nanofiltration membranes with intermediate layers of quaternized cellulose nanocrystal for Mg2+/Li+ separation - Jia-Min Jin; Hao Ye; Tian-Hao Li; Ming-Bang Wu; Lin Liu; Juming Yao (Desalination, 2024)

Vitamin e succinate-glycol chitosan modified copper ferrite nanocomposites for lung cancer: Targeted oxidative stress regulation induces cuproptosis and ferroptosis - Guansong Hu; Weibin Cheng; Miao Gu; Lifeng Hang; Weiyang Yang; Tao Liu; Wuming Li; Xiudong Shi; Min Liu; Junzhang Tian (Chemical Engineering Journal, 2024)

Multidimensional combinatorial screening for high-level production of erythritol in Yarrowia lipolytica - Lei Li; Qianqian Zhang; Ruirui Shi; Mingdong Yao; Kangming Tian; Fuping Lu; Hui-Min Qin (Bioresource Technology, 2024)

Biochar promotes microbial CO2 fixation by regulating feedback inhibition of metabolites - Xiaodi Zhao; Yundong Liu; Li Xie; Xiaohua Fu; Lei Wang; Min-tian Gao; Jiajun Hu (Bioresource Technology, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Ultrasmall copper nanodots eye drops for microenvironment regulation of diabetes retinopathy by relieving hypoxia and inhibiting HIF-1α/VEGF signaling pathway - Min Tian; Zheng Li; Siyan Liu; Zhiyuan Wang; Bo Deng; Yang Cao; Jinchuan Wu; Zhu Zhu; Jun Jiang; Guang Li; Hongbin Lv (Chemical Engineering Journal, 2024)

Using artificial windows to influence occupants’ mood and task performance in windowless spaces - A review - Haiyang Li; Zhen Tian; Sijun Zhang; Min Zou (Building and Environment, 2024)

Complete genome sequence and genetic characterization of a novel segmented RNA virus infecting Nilaparvata lugens - Chao Ning; Zhuang-Xin Ye; Zhong-Tian Xu; Ting Li; Chuan-Xi Zhang; Jian-Ping Chen; Jun-Min Li; Qianzhuo Mao (Archives of Virology, 2024)

A DUF966 gene family member OsDSR3 positively regulates alkali stress tolerance in rice - Xuping Lu; Yan Li; Maryam Akhtar; Caixia Liu; Tianli Ma; Weifang Min; Xiaorong Bai; Yangmengfei She; Liang Chen; Lei Tian; Peifu Li; Chengke Luo (Plant Science, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Genome-guided discovery of two undescribed 6,6-spiroketal polyketides and stereochemical correction of bafilomycins P and Q from the marine-derived Streptomyces sp. SCSIO 66814 - Wenping Ding; Yanqun Li; Xingyu Li; Songbiao Shi; Jiajia Yin; Xinpeng Tian; Min Xiao; Si Zhang; Hao Yin (Phytochemistry, 2024)

Purification and recovery of NaCl from epoxy resin waste salt through an integrated process based on aqueous two-phase systems (ATPS) - Ling Feng; Binghui Tian; Li Chen; Min Yang (Journal of Environmental Chemical Engineering, 2024)

Insight into sodium selenite-induced metabolic reprogramming in response to main seleno-amino acid enrichment in Saccharomyces cerevisiae using metabolomics - Furong Wang; Min Yan; Ting Zhang; Zhen Tian; Xinxin Niu; Zimeng Guo; Xian Wang; Xiaoben Li; Wei Song; Yan'e Luo; Yahong Yuan; Tianli Yue (Food Bioscience, 2024)

Vertically aligned and conformal BN-coated carbon fiber to achieve enhanced thermal conductivity and electrical insulation of a thermal interface material - Min Huang; Zhiqian Wang; Nizao Kong; Biao Li; Chong Ye; Kun Jia; Liqin Fu; Yexin Tian; Donghong Wang; Fei Han (Chemical Engineering Journal, 2024)

Variations in optical properties of water- and methanol-soluble organic carbon in PM2.5 in Tianjin and Handan over the Wintertime of 2018–2020 - Haibiao Chen; Ruizhi Zhou; Li Fang; Honglei Sun; Qiaoyun Yang; Hongya Niu; Junwen Liu; Yingze Tian; Min Cui; Caiqing Yan (Atmospheric Research, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Design and Realization of Electromagnetic Instrument Data Acquisition Circuit for Landslide Detection - Bin Li; Qiang Xu; Tian-xiang Liu; Qiang Cheng; Min-gao Tang; Guang Zheng; Zhuo Wang (Applied Geophysics, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Mechanistic insight into the impact of polystyrene microparticle on submerged plant during asexual propagules germination to seedling: Internalization in functional organs and alterations of physiological phenotypes - Zhiqiang Zhang; Hongwei Yu; Min Tao; Tian Lv; Fuchao Li; Dan Yu; Chunhua Liu (Journal of Hazardous Materials, 2024)

The impact of arbuscular mycorrhizal fungi and endophytic bacteria on peanuts under the combined pollution of cadmium and microplastics - Zi-tian Pu; Dan-dan Wang; Wei-xing Song; Chao Wang; Zhao-yu Li; Ying-long Chen; Tori Shimozono; Zhao-min Yang; Yong-qiang Tian; Zhi-hong Xie (Journal of Hazardous Materials, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

The effect of canagliflozin on gut microbiota and metabolites in type 2 diabetic mice - Li Zeng; Jideng Ma; Tiantian Wei; Hao Wang; Guitao Yang; Chongxiang Han; Tao Zhu; Haoming Tian; Min Zhang (Genes & Genomics, 2024)

Pore Pressure Prediction for High-Pressure Tight Sandstone in the Huizhou Sag, Pearl River Mouth Basin, China: A Machine Learning-Based Approach - Jin Feng; Qinghui Wang; Min Li; Xiaoyan Li; Kaijin Zhou; Xin Tian; Jiancheng Niu; Zhiling Yang; Qingyu Zhang; Mengdi Sun (Journal of Marine Science and Engineering, 2024)
A growing number of large data sets have created challenges for the oil and gas industry in predicting reservoir parameters and assessing well productivity through efficient and cost-effective techniques. The design of drilling plans for a high-pressure tight-sand reservoir requires accurate estimations of pore pressure (Pp) and reservoir parameters. The objective of this study is to predict and compare the Pp of Huizhou Sag, Pearl River Mouth Basin, China, using conventional techniques and machine learning (ML) algorithms. We investigated the characteristics of low-permeability reservoirs by observing well-logging data sets and cores and examining thin sections under a microscope. In the reservoir zone, the average hydrocarbon saturation is 55%, and the average effective porosity is 11%. The tight sandstone reservoirs consist of fine- to extremely fine-grained argillaceous feldspathic sandstone. The mean absolute error for reservoir property prediction is 1.3%, 2.2%, and 4.8%, respectively, for effective porosity, shale volume, and water saturation. Moreover, the ML algorithm was employed to cross-check the validity of the prediction of Pp. Combining conventional and ML techniques with the core data demonstrates a correlation coefficient (R2) of 0.9587, indicating that ML techniques are the most effective in testing well data. This study shows that ML can effectively predict Pp at subsequent depths in adjacent geologically similar locations. Compared to conventional methods, a substantial data set and ML algorithms improve the precision of Pp predictions.

Meta-analyzing the mechanism of pyrogenic biochar strengthens nitrogen removal performance in sulfur-driven autotrophic denitrification system: Evidence from metatranscriptomics - Wen-Jie Ma; Han-Min Zhang; Zi-Shang Ma; Xiu-Jia You; Xin-Yue Wei; Yue Li; Yu Tian (Water Research, 2024)

Impact of aerosol-boundary layer interactions on PM2.5 pollution during cold air pool events in a semi-arid urban basin - Min Zhang; Pengfei Tian; Yiyang Zhao; Xin Song; Jiening Liang; Jiayun Li; Zhida Zhang; Xu Guan; Xianjie Cao; Yan Ren; Jinsen Shi; Lei Zhang (Science of The Total Environment, 2024)

Biodegradation of microplastics derived from controlled release fertilizer coating: Selective microbial colonization and metabolism in plastisphere - Hongyu Tian; Lingyun Wang; Xiaofan Zhu; Min Zhang; Lei Li; Zhiguang Liu; Soroush Abolfathi (Science of The Total Environment, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Imbalance of T follicular helper cell subsets trigger the differentiation of pathogenic B cells in idiopathic membranous nephropathy - Bishun Deng; Huijie Huang; Li Deng; Ziling Zhao; Miao Liu; Haibiao Lin; Xiaowan Wang; Ruimin Tian; Xiaoxin Tu; Anping Peng; Enyu Liang; Kun Bao; et al. (Inflammation Research, 2024)

Distribution and influencing factors of atmospheric nitrogen oxides (NOx) over the east coast of China in spring: Indication of the sea as a sink of the atmospheric NOx - Ye Tian; Hui-Min Jian; Chun-Ying Liu; Jiang-Chen Gong; Pei-Feng Li; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

DNAzyme-driven bipedal DNA walker and catalytic hairpin assembly multistage signal amplified electrochemical biosensor based on porous AuNPs@Zr-MOF for detection of Pb2+ - Ruirui Liang; Jie Dong; Jiayi Li; Huali Jin; Min Wei; Tian Bai; Wenjie Ren; Yiwei Xu; Baoshan He; Zhiguang Suo (Food Chemistry, 2024)

Exosome-shuttled FTO from BM-MSCs contributes to cancer malignancy and chemoresistance in acute myeloid leukemia by inducing m6A-demethylation: A nano-based investigation - Ruirui Kou; Tian Li; Caizhu Fu; Duanfeng Jiang; Yue Wang; Jie Meng; Ruilan Zhong; Changjiu Liang; Min Dong (Environmental Research, 2024)

Development of Data Acquisition Software for Electromagnetic Instruments in Landslide Detection - Bin Li; Qiang Xu; Tian-Xiang Liu; Qiang Cheng; Min-gao Tang; Guang Zheng; Hang Lei (Applied Geophysics, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Designing step-scheme AgI decorated Ta2O5-x heterojunctions for boosted photodegradation of organic pollutants - Min Ma; Hezheng Sun; Xin Yu; Changhui Xin; Jing Liu; Junmeng Guo; Mingxue Li; Yajie Tian (Chemosphere, 2024)

Numerical investigation of the tensile behaviors of needle-punched nonwoven geotextiles - Ke-Yi Li; Xiao-Wu Tang; Min-Liang Fei; Qing-Qing Xiang; Tian-Qi Wang (Geotextiles and Geomembranes, 2024)

Eco-friendly and stable triclosan removal from groundwater using peroxyacetic acid activated with biochar produced from saccharification residues - Wang Kai Tong; Chaomeng Dai; Chenyan Jia; Jiajun Hu; Min-tian Gao; Jixiang Li; Jun Bo Zhang; Han Tang; Yucang Liang; Wei Teng; Zhi Li; Shuguang Liu; et al. (Chemical Engineering Journal, 2024)

Self-regulation of bed temperature field of the fixed-bed reactor unit by composite-filled oxygen carriers for chemical looping combustion of methane - Xianming Cheng; Zonghao Xu; Li Jiang; Min Zheng; Zhenhua Gu; Dong Tian; Kongzhai Li; Hua Wang (Chemical Engineering Journal, 2024)

Sustainable structural polysaccharides conversion: How does DES pretreatment affect cellulase adsorption, thereby improving enzymatic digestion of lignocellulose? - Min Zhou; Yuxuan Feng; Haidong Li; Xingjun Tian (Carbohydrate Polymers, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Chemical constituents from the aerial parts of Orychophragmus violaceus - Zanxin Xu; Li Bin; Tian Ying; Li Min; Dong Junxing; Zhang Guangjie (Natural Product Research, 2024)

Integration of transcriptome and metabolome reveals molecular mechanisms responsive to cold stress in gynogenetic mrigal carp (Cirrhinus mrigala) - Hongqing Li; Wuhui Li; Jisen Su; Zexun Zhou; Yan Miao; Xuelei Tian; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Huirong Yang; Shaojun Liu (Aquaculture, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Basin-scale reconstruction of late Pleistocene-Holocene fluvial landform evolution and its mechanisms in transitional areas between Taihang Mountain and North China Plain - Yan Tian; Panpan Chen; Peng Lu; Ye Li; Hui Wang; Liang Zhou; Xiaohu Zhang; Shugang Yang; Xingguo Zhang; Xiaoyu Chai; Haiguo Zhai; Min Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Microplastics in the atmosphere: Adsorb on leaves and their effects on the phyllosphere bacterial community - Libo Xu; Kang Li; Xinyi Bai; Guangbao Zhang; Xudong Tian; Qian Tang; Mengjun Zhang; Min Hu; Yi Huang (Journal of Hazardous Materials, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Generation and origin of persistent high excess pore water pressure in debris flows - Zi-Ming Ye; Ze-Min Xu; Bin Li; Xiao Su; Gui-E Shi; Jing-Kai Meng; Lin Tian (Geomorphology, 2024)

Complete genome sequence of a novel robigovirus infecting Mentha arvensis - Hai-Tao Weng; Yi-Yuan Li; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li; Zhong-Tian Xu (Archives of Virology, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

A novel non-centrifugal sugar prepared from tiger nut (Cyperus esculentus L.) meal: Preparation methods and comparison with sugarcane - Run-Yang Zhang; Xin-Yun Huang; Peng-Xiao Chen; Tian Li; Meng-Meng Jiang; Yi-Long Wang; Wen-Xue Zhu; Hua-Min Liu (Food Research International, 2023)

Bisphenol A and its analogue bisphenol S exposure reduce estradiol synthesis via the ROS-mediated PERK/ATF4 signaling pathway - Zhou Li; Chen Chen; Pan Ying; Gu Ji-jun; Dou Lian-jie; Huang Dan; Zou Xuan-min; Guan Tian-yue; Zhang Chao; Hao Jia-hu (Food and Chemical Toxicology, 2023)

Low-temperature structural deformation and fragmentation of lead styphnate by in-situ experiments and calculation - Momang Tian; Qian Yu; Yuewen Lu; Ji-Min Han; Li Yang (Chemical Engineering Journal, 2023)

Purification of Galacto-oligosaccharide (GOS) by fermentation with Kluyveromyces lactis and Interaction between GOS and casein under simulated acidic fermentation conditions - Zhihui LI; Lai Tian-tian; Tariq Aziz; Zhang Min; Abid Sarwar; Yang Zhennai; Metab Alharbi; Abdulrahman Alshammari; Abdullah F Alasmari (World Journal of Microbiology and Biotechnology, 2023)

Promoting short-chain fatty acids production from sewage sludge via acidogenic fermentation: Optimized operation factors and iron-based persulfate activation system - Faxin Liu; Wen Cheng; Jianping Xu; Min Wang; Tian Wan; Jiehui Ren; Dong Li; Qiqi Xie (Chemosphere, 2023)

Shifting enzyme activity and microbial composition in sediment coregulate the structure of an aquatic plant community under polyethylene microplastic exposure - Zhiqiang Zhang; Hongwei Yu; Min Tao; Tian Lv; Dexiang Li; Dan Yu; Chunhua Liu (Science of The Total Environment, 2023)

Enhancing degradation of organic matter in microbial electrolytic cells coupled with anaerobic digestion (MEC-AD) systems by carbon-based materials - Mengmeng Li; Qun Zhang; Yang Liu; Jiachen Zhu; Faqian Sun; Min-Hua Cui; He Liu; Tian C. Zhang; Chongjun Chen (Science of The Total Environment, 2023)

Room-temperature orbit-transfer torque enabling van der Waals magnetoresistive memories - Zhen-Cun Pan; Dong Li; Xing-Guo Ye; Zheng Chen; Zhao-Hui Chen; An-Qi Wang; Mingliang Tian; Guangjie Yao; Kaihui Liu; Zhi-Min Liao (Science Bulletin, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Interaction and binding mechanism of cyanidin-3-O-glucoside to lysozyme in varying pH conditions: Multi-spectroscopic, molecular docking and molecular dynamics simulation approaches - Hailong Gui; Qiao Jiang; Jinlong Tian; Zang Zhihuan; Shufang Yang; Yiyun Yang; Meili Xin; Min Zhao; Jian Dai; Bin Li (Food Chemistry, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Significant roles of aged dust aerosols on rapid nitrate formation under dry conditions in a semi-arid city - Jiayun Li; Naiyue Zhang; Pengfei Tian; Min Zhang; Jinsen Shi; Yi Chang; Lei Zhang; Zirui Liu; Yuesi Wang (Environmental Pollution, 2023)

Mechanical behavior of round bamboo under transverse local compression - Bei-bei Jin; Ji-ping Hao; Ya-nan Luo; Li-min Tian (Engineering Structures, 2023)

Electrochemical oxidation treatment of reverse osmosis concentrated landfill leachate: Effect of operation parameters and evolution of dissolved organic matter - Ye-Chao Tian; Wen-Xiang Ji; Yu-Ze Han; Ze-Tao Wu; Hai-Ou Song; Ai-Min Li; Wen-Tao Li (Chemical Engineering Journal, 2023)

Genome-wide characterization of mapk gene family in black rockfish Sebastes schlegelii and their expression patterns against Edwardsiella piscicida infection - Xiaoyan Zhang; Yuan Tian; Haohui Yu; Min Cao; Chao Li (Journal of Oceanology and Limnology, 2023)

MD-YOLO: Multi-scale Dense YOLO for small target pest detection - Yunong Tian; Shihui Wang; En Li; Guodong Yang; Zize Liang; Min Tan (Computers and Electronics in Agriculture, 2023)

A hybrid receding horizon optimization and active disturbance rejection control of boiler superheated steam temperature - Shaojie Liu; Huanpao Huang; Donghai Li; Bin Tian; Wenchao Xue; Li Sun; Min Zhu (Process Safety and Environmental Protection, 2023)

Sesquiterpene coumarins from Ferula sinkiangensis and their anti-pancreatic cancer effects - Jia-Lin Wang; Chun-Yan Sang; Jun Wang; Pei-Lin Li; Tian Chai; Mohammad Reza Naghavi; Ya-Min Zhao; Jun-Li Yang (Phytochemistry, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Increased ascorbic acid synthesis by overexpression of AcGGP3 ameliorates copper toxicity in kiwifruit - Xiaoying Liu; Chang Cheng; Yan Min; Xiaodong Xie; Abu Naim Md. Muzahid; Haiyan Lv; Hua Tian; Congxiao Zhang; Can Ye; Shifeng Cao; Peng Chen; Caihong Zhong; et al. (Journal of Hazardous Materials, 2023)

RETRACTED: Construction of a novel ursolic acid-based supramolecular gel for efficient removal of iodine from solution - Zhichun Shi; Xiuqi Huang; Yingnan Zhao; Jun Li; Yan Qing Tian; Piao Piao Zhang; Min Zhu; Ming Zhao (Environmental Research, 2023)

Extracellular vesicle–encapsulated miR-10a-5p derived from MDSCs restrains germinal center B cells in experimental Sjögren’s syndrome - Huimin Zhou; Qiugang Zhu; Zhenwei Mao; Min Li; Yue Zhang; Jun Yang; Jie Ma; Jie Tian; Shengjun Wang (Immunologic Research, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Effects of functional group loss on biochar activated persulfate in-situ remediation of phenol pollution in groundwater and its countermeasures - Chaomeng Dai; Jun Bo Zhang; Min-tian Gao; Yalei Zhang; Jixiang Li; Jiajun Hu (Journal of Environmental Management, 2023)

Lobetyolin, a Q-marker isolated from Radix Platycodi, exerts protective effects on cisplatin-induced cytotoxicity in HEK293 cells - Yun-yi Hou; Si-min Qi; Jing Leng; Qiong Shen; Shan Tang; Jing-tian Zhang; Jun-nan Hu; Shuang Jiang; Wei Li (Journal of Natural Medicines, 2023)

Genetic characterization of Sus scrofa papillomavirus type 1 from domestic pigs in Guangxi Province, China - Yuying Li; Xinyu Zhang; Chenchen Zhao; Xiaoxiao Lei; Haixin Huang; Yaokai Shi; Chengkai Li; Jingshan Bi; Wenchao Sun; Tian Lan; Min Zheng (Brazilian Journal of Microbiology, 2023)

Four organosulfur compounds from the seeds of Capsella bursa-pastoris and their anti-inflammatory activities - Zhen-Zhen Wei; Ti-Qiang Zhou; Zi-Ming Xia; Si-Fan Liu; Min Li; Guang-Jie Zhang; Ying Tian; Bin Li; Lin Wang (Natural Product Research, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Paleoclimatic and anthropogenic impacts on the environment of Southwest China since 33 ka based on multiproxy analysis of karst depression deposits - Xing Tian; Xiaoyong Long; Shu’e Luo; Min Cao; Ji Li; Yuchuan Sun; Sibo Zeng; Ze Wu; Chuan Liu; Lidan Lei; Thomas J. Algeo; Yongjun Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Bioremediation system consisted with Leclercia adecarboxylata and nZVI@Carbon/Phosphate for lead immobilization: The passivation mechanisms of chemical reaction and biological metabolism in soil - Zedong Teng; Xin Zhao; Bojie Jia; Liangjun Ye; Shaojing Tian; Huiyuan Guo; Yali Guo; Xiaonan Ji; Tinggang Li; Min Li (Journal of Environmental Management, 2023)

Observation of nitrogen oxide-influenced chlorine chemistry and source analysis of Cl2 in the Yangtze River Delta, China - Fangbing Li; Dan Dan Huang; Wei Nie; Yee Jun Tham; Shengrong Lou; Yuanyuan Li; Linhui Tian; Yuliang Liu; Min Zhou; Haichao Wang; Liping Qiao; Hongli Wang; et al. (Atmospheric Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Hyper-thermophilic anaerobic pretreatment enhances the removal of transferable oxazolidinone and phenicol cross-resistance gene optrA in enterococci - Tiantian Tian; Xiaoxiao Yang; Shihai Liu; Ziming Han; Wei Qiao; Jiuyi Li; Min Yang; Yu Zhang (Waste Management, 2023)

Global-scale no-tillage impacts on soil aggregates and associated carbon and nitrogen concentrations in croplands: A meta-analysis - Peng Li; Duo Ying; Jing Li; Jianjun Deng; Chunkai Li; Shanyi Tian; Gen Zhao; Choufei Wu; Jiaguo Jiao; Min Jiang; Feng Hu (Science of The Total Environment, 2023)

Effect of curcumin on the formation of polycyclic aromatic hydrocarbons in grilled chicken wings - Huixin Tian; Jing Yu; Min Li; Jing Li; Yifeng Lu; Xiaobo Yu; Shaoyan Lin; Xianming Zeng; Xinglian Xu; Minyi Han (Food Chemistry, 2023)

The functions of two GSDMEs in pyroptosis of common carp (Cyprinus carpio L.) in canonical and non-canonical inflammasome pathways - Hui Wang; Rongrong Liu; Yue Zhao; Yu Liu; Min Tian; Shijuan Shan; Guiwen Yang; Hua Li (Fish & Shellfish Immunology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Environmental biotransformation mechanisms by flavin-dependent monooxygenase: A computational study - Fangjie Guo; Yilin Tian; Shujing Ji; Hao Min; Wen Ding; Haiying Yu; Yingqi Li; Li Ji (Chemosphere, 2023)

The contradictory roles of tightly bound and loosely bound extracellular polymeric substances of activated sludge in trimethoprim adsorption process - You Ma; Tian-Yu Li; Han Meng; Guo-Xiang Wang; Li-Min Zhang; Guo-Zheng Jia; Jie Ma; Yan Xiao; Wei-Hua Li; Wen-Ming Xie (Journal of Environmental Management, 2023)

Phenylpropanoids from the Nitraria tangutorum fruit as glycerol phosphate dehydrogenase inhibitors through in vitro, in silico and in vivo studies - Zhi-Xiang Liu; Lin-Lin Yuan; Nan Zhang; Min Zhao; Yue Li; Ming-Yue Zhao; Yu-Meng Wang; Zi-Zhuo Wang; Yang-Yang Zhang; Jin-Long Tian (Food Bioscience, 2023)

Biochar modification to enhance arsenic removal from water: a review - Luping Tian; Hao Li; Zhaofeng Chang; Ni Liang; Min Wu; Bo Pan (Environmental Geochemistry and Health, 2023)

Juvenile hormone regulates the photoperiodic plasticity of elytra coloration in the ladybird Harmonia axyridis - Jia‐Xu Li; Zhong Tian; Xing‐Feng Liu; Bei Li; Hao‐Min An; Colin S. Brent; Jia‐Lu Wang; Xiao‐Ping Wang; Wen Liu (Molecular Ecology, 2023)
Many animals, including insects, exhibit plasticity of body colour in response to environmental changes. Varied expression of carotenoids, major cuticle pigments, significantly contributes to body colour flexibility. However, the molecular mechanisms by which environmental cues regulate carotenoid expression remain largely unknown. In this study, we used the ladybird Harmonia axyridis as a model to investigate the photoperiodic‐responsive plasticity of elytra coloration and its endocrine regulation. It was found that H. axyridis females under long‐day conditions develop elytra that are much redder than those under short‐day conditions, resulting from the differential accumulation of carotenoids. Exogenous hormone application and RNAi‐mediated gene knockdown indicate that carotenoid deposition was directed through the juvenile hormone (JH) receptor‐mediated canonical pathway. Moreover, we characterized an SR‐BI/CD36 ( SCRB ) gene SCRB10 as the carotenoid transporter responding to JH signalling and regulating the elytra coloration plasticity. Taken together, we propose that JH signalling transcriptionally regulates the carotenoid transporter gene for the photoperiodic coloration plasticity of elytra in the beetles, which reveals a novel role of the endocrine system in the regulation of carotenoid‐associated animal body coloration under environmental stimuli.

Unraveling the evolution of dissolved organic matter in full-scale A/A/O wastewater treatment process using size exclusion chromatography with PARAFAC and nonnegative matrix factorization analysis - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Wen-Xiang Ji; Qing Zhou; Jun Li; Wen-Tao Li (Water Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

WITHDRAWN: Construction and evaluation of risk prediction model for kidney injury in patients treated with PD-1 inhibitors - Peiyu Lu; Li Tian; Aihua Wu; Hua Zhou; Min Yang (Toxicology and Applied Pharmacology, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

First evidence and potential sources of novel brominated flame retardants and BDE 209 in the deepest ocean - Jingqian Xie; Gaoxin Zhang; Qiang Wu; Min Luo; Duofu Chen; Yu Zhang; Lisheng He; Yingming Li; Qinghua Zhang; Tian Lin; Guibin Jiang (Journal of Hazardous Materials, 2023)

Biodegradable, anti-freezing and self-healable hydrogel mulch film for weed control - Shan-Shan Li; Song-Bo Wang; Yu Chen; Qi-Shun Zhu; Ling-Min Lan; Huaitian Bu; Tian Hu; Gang-Biao Jiang (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Petrogenesis and Tectonic Implications of the Late Silurian–Early Devonian Bimodal Intrusive Rocks in the Central Beishan Orogenic Belt, NW China: Constraints by Petrology, Geochemistry and Hf Isotope - Jian Tian; Hou-Tian Xin; Xue-Jian Teng; Min Li; Qun-An Liao; Yong Zhang; Bang-Fang Ren (Journal of Earth Science, 2023)

Effects of tungsten on vacancy aggregation behavior and its induction for interstitial and vacancy migration in tantalum–tungsten alloys: A first-principles study - Huaigu Tian; Hongjuan Zhu; Yanfei Zheng; Shuangsuo Mao; Xiaohua Zhou; Zelin Cao; Min Pan; Shulong Wen; Rusong Li (Annals of Nuclear Energy, 2023)

Effect of Tip Rake Distribution on the Hydrodynamic Performance of Non-Planar Kappel Propeller - Chen-Wei Chen; Xu-Peng Chen; Zhao-Ye Zhou; Li-Wan Chen; Chi Zhang; Tian-Jiang Zheng; Hua-Min Li (Journal of Marine Science and Engineering, 2023)
Taking advantage of end-plate effects to enhance propeller efficiency is engaging. This paper applied a 4-order B-spline curve to design the rake distribution of Kappel propellers using five types of Kappel propellers that each possesses different tip rakes, and one type has no constructed end-plate. The RANS method coupled with the γ transition model was utilized to analyze the open-water performance of the six propellers, considering cavitating flow. It was found that the tip rake is conducive to the thrust capacity of the Kappel propellers, mostly improving the propulsion efficiency by 2.5% at a designed advance speed with the appropriate tip rake. The increase in the tip rake will magnify the low-pressure value and area on the suction side blade surface, together with the phenomenon of the stretching tip vortex and the inhibition of wake vortex contraction, which are both beneficial to the elevation of propulsion efficiency. However, the sheet cavitation behavior of the six propellers aggravates as the tip rake rises. Accordingly, the reasonable range of a tip rake for the design of a Kappel propeller in favor of the propulsion performance is suggested in this paper, exhibiting the promising potential of energy savings for the application to marine vehicles.

Comprehensive treatment strategy for diesel truck exhaust - Tian Li; Hai-Li Yang; Le-Tian Xu; Yu-Ting Zhou; Yong-Jun Min; Shi-Cheng Yan; Yong-Hui Zhang; Xiao-Ming Wang (Environmental Science and Pollution Research, 2023)

Storms dominate the erosion of the Yangtze Delta and southward sediment transport - Shilun Yang; Tjeerd J. Bouma; Kehui Xu; Benwei Shi; Haifei Yang; Wenxiang Zhang; Xiangxin Luo; Peng Li; Yuanguang Huang; Min Tian; Leicheng Guo; Zhijun Dai (Science Bulletin, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Characterization of aroma-active compounds changes of Xiecun Huangjius with different aging years based on odor activity values and multivariate analysis - Min Li; Ping Zhan; Peng Wang; Honglei Tian; Jingzhang Geng; Lixia Wang (Food Chemistry, 2023)

Lignosulfonate-Based Hybrid Hydrogels Functionalized with Hyperbranched Polyamide Amine as Ultra-High-Capacity Adsorbent for Congo Red Removal from Aqueous Solutions - Ruichao Li; Nini Tian; Jiantang Jiang; Doufeng Wu; Min Xia; Huagang Ni; Peng Ye; Xintong Zong; Liang Zong; Yumei Wang (Water, Air, & Soil Pollution, 2023)

Spatio-temporal agglomeration and morphological causes of Shanghai catering clusters - Chuang Tian; Weixin Luan; Hui Wang; Di Yang; Min Su; Zhenchao Zhang; Zeyang Li (Applied Geography, 2023)

Seismic behavior of concrete columns with ends transformed via perforated H-shaped steel and engineered cementitious composite - Chong Bai; Li-min Tian; Ping Yang; Tian-ji Li (Soil Dynamics and Earthquake Engineering, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Assessment and prevention on the potential rockfall hazard of high-steep rock slope: a case study of Zhongyuntai mountain in Lianyungang, China - Zhong-Min Ji; Tian-Li Chen; Fa-Quan Wu; Zhen-Hua Li; Qing-He Niu; Ke-Yi Wang (Natural Hazards, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Effects of multi-resource addition on grassland plant productivity and biodiversity along a resource gradient - Xinxin Guo; Xiaoan Zuo; Eduardo Medina-Roldán; Aixia Guo; Ping Yue; Xueyong Zhao; Jingjuan Qiao; Xiangyun Li; Min Chen; Cunzheng Wei; Tian Yang; Yuguang Ke; et al. (Science of The Total Environment, 2023)

In vitro toxicity assessment of haloacetamides via a toxicogenomics assay - Dong Li; Wen Cheng; Jiehui Ren; Lu Qin; Xing Zheng; Tian Wan; Min Wang (Environmental Toxicology and Pharmacology, 2023)

Structural performance of composite connections with a uniaxial symmetric steel-beam section - Ying-lu Xu; Yao-xuan Su; Yong-fang Shang; Zi-long Liu; Li-min Tian (Engineering Structures, 2023)

Mussel foot inspired bionic adhesive material enhanced by a reconstructed in vitro system for interfacial adhesion - Kai Li; Zitang Xu; Xiaoxiao Liu; Yaojia He; Xiaoke Tian; Xiaoling Xu; Guangxu Bo; Sheng Yuan; Li Xu; Min Yang; Jinyong Yan; Houjin Zhang; et al. (Chemical Engineering Journal, 2023)

Amyloid-like coatings decorated electrodes boost the uranium electro-adsorption from seawater - Hao Ye; Tian-Hao Li; Yu-Qi Huang; Jia-Min Jin; Jin-Yan Fei; Ming-Bang Wu; Juming Yao (Chemical Engineering Journal, 2023)

Lower expression of the equine maternally imprinted gene IGF2R is related to the slow proliferation of hinny embryonic fibroblast in vitro - Xisheng Wang; Nairag Asgenbaatar; Yingchao Shen; Minna Yi; Bilig Zhao; Hong Ren; Toli Davshilt; Tseweendolmaa Ulaangerel; Min Wang; Als Burenbaatar; Shuyue Tian; Bei Li; et al. (Molecular Biology Reports, 2023)

Aloe polysaccharide promotes osteogenesis potential of adipose-derived stromal cells via BMP-2/Smads and prevents ovariectomized-induced osteoporosis - Xue-wei Yao; He-dong Liu; Mao-xian Ren; Tian-lin Li; Wen-kai Jiang; Zhi Zhou; Zhi-yi Liu; Min Yang (Molecular Biology Reports, 2022)
Background Aloe polysaccharide (AP) is a type of an active macromolecule of Aloe vera, which contributes to its function. However, whether AP possesses anti-osteoporosis properties is unknown. Methods Adipose-derived stromal cells were treated with different concentrations of AP. Early and late osteogenesis were, respectively, evaluated by ALP and Alizarin Red S staining. The effect of AP on the processes of adipogenesis inhibition in ADSCs was analyzed by oil red O staining. Western blot was used to assess the expression of osteogenic and adipogenic related factors. Then, Noggin was administered to further confirm the mechanism by which AP promotes the osteogenesis of ADSCs. Finally, 40 female SD rats were classified into a bilateral laparotomy group (Sham group) and three bilateral ovariectomy groups: OVX group, OVX + AP group, and OVX + AP + Noggin group. The bilateral rat femurs were collected to perform micro-CT scanning, HE, Masson trichrome, and Oil red O staining. Results The results indicated that AP could increase ALP expression and calcium deposition. Through molecular mechanisms, AP promotes the protein expression of COL1A1, OPN, and ALP in ADSCs, but downregulates the expression of PPARγ. Also, AP directs ADSCs’ fate by stimulating the BMP2/Smads signaling pathway. In vivo, the rat AP-treated had more trabecular bone than the OVX rat, indicating partial protection from cancellous bone loss after treatment with AP. Conclusion Our results show that AP may promote osteogenesis of ADSCs through BMP-2/Smads signaling pathway and inhibits lipogenic differentiation. Thus, AP might be a promising alternative medicine to treat postmenopausal osteoporosis.

Pollution characteristics and risk assessment of heavy metals in surface water of Manas River, Xinjiang, China - Shaohua He; Bingbing Tian; Fengyu Liu; Junqi Wang; Shuyi Gong; Jianjiang Lu; Min Li (Arabian Journal of Geosciences, 2022)

Association of soft drink and 100% fruit juice consumption with all-cause mortality, cardiovascular diseases mortality, and cancer mortality: A systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Long Ge; Honghao Lai; Qi Wang; Qi Wang; Qian Zhang; Min Yin; Sheng Li; Jinhui Tian; Kehu Yang; Jiancheng Wang (Critical Reviews in Food Science and Nutrition, 2022)

Risk Identification of Heavy Metals in Agricultural Soils from a Typically High Cd Geological Background Area in Upper Reaches of the Yangtze River - Xiaosong Tian; Guanqun Chai; Qing Xie; Min Fan; Song Qin; Chengwu Fan; Yalong Gong; Jinhu Liu; Guanghui Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Structural and functional MRI evidence for significant contribution of precentral gyrus to flexible oculomotor control: evidence from the antisaccade task - Zhenlan Jin; Dong-gang Jin; Min Xiao; Aolin Ding; Jing Tian; Junjun Zhang; Ling Li (Brain Structure and Function, 2022)
Antisaccade task requires inhibition of a prepotent prosaccade to a peripheral target and initiation of a saccade to the opposite location, and, therefore, is used as a tool to investigate behavioral adjustment. The frontal and parietal cortices are both known for their activation during saccade generation, but it is unclear whether their neuroanatomical characteristics also contribute to antisaccades. Here, we took antisaccade cost (antisaccade latency minus prosaccade latency) as an index for additional time for generating antisaccades. Fifty-eight participants conducted pro and antisaccade tasks outside the magnetic resonance imaging (MRI) scanner and their structural MRI (sMRI) data were also collected to explore brain regions neuroanatomically related to antisaccade cost. Then, twelve participants performed saccade tasks in the scanner and their task-state functional MRI (fMRI) data were collected to verify the activation of structurally identified brain regions during the saccade generation. Voxel-based morphometry (VBM) results revealed that gray matter volume (GMV) of the left precentral gyrus and the left insula were positively correlated with the antisaccade cost, which was validated by the prediction analysis. Brain activation results showed the activation of the precentral during both pro and antisaccade execution period, but not the insula. Our results suggest that precentral gyrus and insula play vital roles to antisaccade cost, but possibly in different ways. The insula, a key node of the salience network, possibly regulates the saliency processing of the target, while the precentral gyrus possibly mediates the generation of saccades. Our study especially highlights an outstanding role of the precentral gyrus in flexible oculomotor control.

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

Metabolomic profiling of five hulless barley (Hordeum vulgare L.) with different - Lijing Liang; Wenbo Li; Min Tian; Jiajia Pan; Zongyun Feng (Genetic Resources and Crop Evolution, 2022)

Kai-Xin-San Inhibits Tau Pathology and Neuronal Apoptosis in Aged SAMP8 Mice - Ya-Nan Jiao; Jing-Sheng Zhang; Wen-Jun Qiao; Shu-Yu Tian; Yi-Bin Wang; Chun-Yan Wang; Yan-Hui Zhang; Qi Zhang; Wen Li; Dong-Yu Min; Zhan-You Wang (Molecular Neurobiology, 2022)
Alzheimer’s disease (AD) is an age-related neurological disorder. Currently, there is no effective cure for AD due to its complexity in pathogenesis. In light of the complex pathogenesis of AD, the traditional Chinese medicine (TCM) formula Kai-Xin-San (KXS), which was used for amnesia treatment, has been proved to improve cognitive function in AD animal models. However, the active ingredients and the mechanism of KXS have not yet been clearly elucidated. In this study, network pharmacology analysis predicts that KXS yields 168 candidate compounds acting on 863 potential targets, 30 of which are associated with AD. Enrichment analysis revealed that the therapeutic mechanisms of KXS for AD are associated with the inhibition of Tau protein hyperphosphorylation, inflammation, and apoptosis. Therefore, we chose 7-month-old senescence-accelerated mouse prone 8 (SAMP8) mice as AD mouse model, which harbors the behavioral and pathological hallmarks of AD. Subsequently, the potential underlying action mechanisms of KXS on AD predicted by the network pharmacology analyses were experimentally validated in SAMP8 mice after intragastric administration of KXS for 3 months. We observed that KXS upregulated AKT phosphorylation, suppressed GSK3β and CDK5 activation, and inhibited the TLR4/MyD88/NF-κB signaling pathway to attenuate Tau hyperphosphorylation and neuroinflammation, thus suppressing neuronal apoptosis and improving the cognitive impairment of aged SAMP8 mice. Taken together, our findings reveal a multi-component and multi-target therapeutic mechanism of KXS for attenuating the progression of AD, contributing to the future development of TCM modernization, including KXS, and broader clinical application. Graphical abstract

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report - Qiu-Hong Shu; Shu-De Li; Ming Tian; Yong Meng; Shu-Mei-Qi He; Min Zhu; Miao-Miao Wang; Wen-Lin Wang (Acta Parasitologica, 2022)
Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted from lungs and muscles. The morphology of adult worms was characterized by microscopy and molecular identification was done by polymerase chain reaction, followed by sequencing of cox1 and ITS2 genes. Phylogenetic analysis was done by maximum parsimony method. Results A total of 447 crabs were captured from the streams of Tongchang Town, Jinping County, Yunnan Province, China. The infection rate was found to be 41% (186 out of 447 crabs). The metacercariae of Paragonimus skrjabini was identified by the characteristics round or spherical encysted form measuring 410 to 460 × 400 to 460 µm. After animal infection in SD rats, adults were presumptively confirmed to be P. skrjabini , which was also confirmed by gene amplification and sequence analysis of cox1 and ITS2 regions. Paragonimus skrjabini clustered with previously reported P. skrjabini from Yunnan and Vietnam. The confidence values of their branches were > 95%. Phylogenetic analysis of the ITS2 region revealed two distinct clusters with distinct geographical grouping. Phylogenetic analysis with the combined data sets reiterated the geographical grouping with P. skrjabini from Yunnan clustering with strains from Vietnam. Conclusion Metacercariae of P. skrjabini was discovered in freshwater crabs in Yunnan province, China, and the strains were phylogenetically related to P. skrjabini from Vietnam.

Three new ester glycosides with cytotoxic activity from the seeds of Caesalpinia sappan - Min Wang; Juan Tan; Jun Chen; Tian Xie; Liang-Mo Lin; Li-Li Zhong; Xing-Jun Cai; Qiong-Shi Wu (Natural Product Research, 2021)

LncRNA TUG1 exhibits pro-fibrosis activity in hypertrophic scar through TAK1/YAP/TAZ pathway via miR-27b-3p - Xian-Min Li; Wen-Yuan Yu; Qi Chen; Hui-Ru Zhuang; Su-Yue Gao; Tian-Lan Zhao (Molecular and Cellular Biochemistry, 2021)

Diversity and function of rhizosphere microorganisms between wild and cultivated medicinal plant Glycyrrhiza uralensis Fisch under different soil conditions - Zhou-Yan Dong; Manik Prabhu Narsing Rao; Tian-Jiang Liao; Li Li; Yong-Hong Liu; Min Xiao; Osama Abdalla Abdelshafy Mohamad; Yue-Ying Tian; Wen-Jun Li (Archives of Microbiology, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Tornado-resisting design speeds of nuclear power plants in China - Yuji Tian; Bo Li; Qingshan Yang; Min Liu (Natural Hazards, 2021)

Experimental Research on Adsorption Kinetic Characteristics of CH4, CO2, and N2 in Coal from Junggar Basin, China, at Different Temperatures - Wanjie Sun; Haifei Lin; Shugang Li; Xiangguo Kong; Hang Long; Min Yan; Yang Bai; Jiamin Tian (Natural Resources Research, 2021)

First detection and complete genome analysis of the Lyon IARC polyomavirus in China from samples of diarrheic cats - Yuying Li; Haixin Huang; Tian Lan; Wei Wang; Jie Zhang; Min Zheng; Liang Cao; Wenchao Sun; Huijun Lu (Virus Genes, 2021)

Mapping QTL for leaf pigment content at dynamic development stage and analyzing Meta-QTL in rice - Lamei Li; Youlin Peng; Shiwen Tang; Dejin Yu; Min Tian; Faping Guo; Yongjun Chen; Guotao Yang; Xuechun Wang; Yungao Hu (Euphytica, 2021)

A calculation model of the normal coefficient of restitution based on multi-factor interaction experiments - Zhong-Min Ji; Zhi-Jian Chen; Qing-He Niu; Ting-Hui Wang; Tian-Jun Wang; Tian-Li Chen (Landslides, 2021)

The metabolic and immunological characteristics of pregnant women with COVID-19 and their neonates - Jingjiao Zhou; Yudie Wang; Juan Zhao; Lixing Gu; Cheng Yang; Jun Wang; Heng Zhang; Yu Tian; Hu Tuo; Dan Li; Min Wei; Bing He (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Antioxidant and anti-inflammatory constituents from Flos populi - Yong Hou; Guangjie Zhang; Min Li; Bowen Li; Li Chen; Ying Tian; Shijun Liu; Bin Li; Junxing Dong (Natural Product Research, 2021)

Postsynaptic Targeting and Mobility of Membrane Surface-Localized hASIC1a - Xing-Lei Song; Di-Shi Liu; Min Qiang; Qian Li; Ming-Gang Liu; Wei-Guang Li; Xin Qi; Nan-Jie Xu; Guang Yang; Michael Xi Zhu; Tian-Le Xu (Neuroscience Bulletin, 2021)
Acid-sensing ion channels (ASICs), the main H + receptors in the central nervous system, sense extracellular pH fluctuations and mediate cation influx. ASIC1a, the major subunit responsible for acid-activated current, is widely expressed in brain neurons, where it plays pivotal roles in diverse functions including synaptic transmission and plasticity. However, the underlying molecular mechanisms for these functions remain mysterious. Using extracellular epitope tagging and a novel antibody recognizing the hASIC1a ectodomain, we examined the membrane targeting and dynamic trafficking of hASIC1a in cultured cortical neurons. Surface hASIC1a was distributed throughout somata and dendrites, clustered in spine heads, and co-localized with postsynaptic markers. By extracellular pHluorin tagging and fluorescence recovery after photobleaching, we detected movement of hASIC1a in synaptic spine heads. Single-particle tracking along with use of the anti-hASIC1a ectodomain antibody revealed long-distance migration and local movement of surface hASIC1a puncta on dendrites. Importantly, enhancing synaptic activity with brain-derived neurotrophic factor accelerated the trafficking and lateral mobility of hASIC1a. With this newly-developed toolbox, our data demonstrate the synaptic location and high dynamics of functionally-relevant hASIC1a on the surface of excitatory synapses, supporting its involvement in synaptic functions.

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Treatment via the Living Machine system of blackwater collected from septic tanks: effect of different plant groups in the systems - Li Tian; Lu Jinzhong; Yang Shenglin; Ye Zhourong; Zhao Min; Kong Hainan; Zheng Xiangyong (Environment, Development and Sustainability, 2021)

3,5,4′-Trimethoxy-trans-stilbene loaded microemulsion for cutaneous melanoma therapy by transdermal drug delivery - Jun-Yong Wu; Jia-Xin Cai; Yong-Jiang Li; Xiong-Bin Hu; Xin-Yi Liu; Jie-Min Wang; Tian-Tian Tang; Da-Xiong Xiang (Drug Delivery and Translational Research, 2021)

Effects of rotational and continuous overgrazing on newly assimilated C allocation - Min Liu; Shengnan Ouyang; Yuqiang Tian; Shuhai Wen; Yan Zhao; Xiaobing Li; Taoge-tao Baoyin; Yakov Kuzyakov; Xingliang Xu (Biology and Fertility of Soils, 2021)

Foundation species across a latitudinal gradient in China - Xiujuan Qiao; Jiaxin Zhang; Zhong Wang; Yaozhan Xu; Tianyang Zhou; Xiangcheng Mi; Min Cao; Wanhui Ye; Guangze Jin; Zhanqing Hao; Xugao Wang; Xihua Wang; et al. (Ecology, 2021)
Foundation species structure forest communities and ecosystems but are difficult to identify without long‐term observations or experiments. We used statistical criteria––outliers from size‐frequency distributions and scale‐dependent negative effects on alpha diversity and positive effects on beta diversity––to identify candidate foundation woody plant species in 12 large forest‐dynamics plots spanning 26 degrees of latitude in China. We used these data (1) to identify candidate foundation species in Chinese forests, (2) to test the hypothesis––based on observations of a midlatitude peak in functional trait diversity and high local species richness but few numerically dominant species in tropical forests––that foundation woody plant species are more frequent in temperate than tropical or boreal forests, and (3) to compare these results with data from the Americas to suggest candidate foundation genera in northern hemisphere forests. Using the most stringent criteria, only two species of Acer , the canopy tree Acer ukurunduense and the shrubby treelet Acer barbinerve , were identified in temperate plots as candidate foundation species. Using more relaxed criteria, we identified four times more candidate foundation species in temperate plots (including species of Acer , Pinus , Juglans , Padus , Tilia , Fraxinus , Prunus , Taxus , Ulmus , and Corlyus ) than in (sub)tropical plots (the treelets or shrubs Aporosa yunnanensis , Ficus hispida , Brassaiopsis glomerulata , and Orophea laui ). Species diversity of co‐occurring woody species was negatively associated with basal area of candidate foundation species more frequently at 5‐ and 10‐m spatial grains (scale) than at a 20‐m grain. Conversely, Bray‐Curtis dissimilarity was positively associated with basal area of candidate foundation species more frequently at 5‐m than at 10‐ or 20‐m grains. Both stringent and relaxed criteria supported the hypothesis that foundation species are more common in mid‐latitude temperate forests. Comparisons of candidate foundation species in Chinese and North American forests suggest that Acer be investigated further as a foundation tree genus.

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Knockdown of TLR4 Represses the Paraquat-Induced Neuroinflammation and Microglial M1 Polarization - Min Huang; Yingying Li; Tian Tian; Kai Wang; Yifan Wang; Weiguang Yan; Huifang Yang (Neurotoxicity Research, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

HMGB1 Mediates Paraquat-Induced Neuroinflammatory Responses via Activating RAGE Signaling Pathway - Min Huang; Muzhen Guo; Kai Wang; Kexin Wu; Yingying Li; Tian Tian; Yifan Wang; Weiguang Yan; Zhijun Zhou; Huifang Yang (Neurotoxicity Research, 2020)

Association Between MTHFR Gene Common Variants, Serum Homocysteine, and Risk of Early-Onset Coronary Artery Disease: A Case–Control Study - Shao-Yan Zhang; Chao Xuan; Xue-Chun Zhang; Jie Zhu; Kang Yue; Peng Zhao; Guo-Wei He; Li-Min Lun; Qing-Wu Tian (Biochemical Genetics, 2020)

Rapid detection of Anguina agrostis by loop-mediated isothermal amplification - Lu-zhen Yu; Shao-yi Song; Cui Yu; Bin-bin Jiao; Yi-min Tian; You-jun Li (European Journal of Plant Pathology, 2020)

Comparative genomics analysis of Nitriliruptoria reveals the genomic differences and salt adaptation strategies - Dai-Di Chen; Ye Tian; Jian-Yu Jiao; Xiao-Tong Zhang; Yong-Guang Zhang; Zhou-Yan Dong; Meng-Jie Xiong; Min Xiao; Wen-Sheng Shu; Wen-Jun Li (Extremophiles, 2020)

Interactions between intercropped Avena sativa and Agropyron cristatum for nitrogen uptake - Min Liu; Huimin Li; Jingjing Song; Minghua Song; Na Qiao; Yuqiang Tian; Yanjie Liu; Haishan Niu (Plant and Soil, 2020)

Effects of high-intensity interval training on adipose tissue lipolysis, inflammation, and metabolomics in aged rats - Lei Sun; Fang-Hui Li; Tao Li; Zhu Min; Luo-Dan Yang; Hao-En Gao; Da-Shuai Wu; Tian Xie (Pflügers Archiv - European Journal of Physiology, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Differential expression of activin β A and β B genes in female allotriploid and diploid red crucian carp Carassius auratus red var - Min Tao; Hong Hu; Lu Huang; Shengnan Li; Liujiao Yuan; Tian Zhou; Can Song; Rurong Zhao; Shaojun Liu (Journal of Fish Biology, 2019)
activin β A and β B from diploid and allotriploid crucian carp were cloned.The differential expression of activin β A and β B genes in female allotriploid and diploid red crucian carp Carassius auratus red var. were studied and found to be expressed in all the tested tissues; particularly, the expression of activin β A and β B was elevated in the ovaries of allotriploids and differential expression in pituitaries during the non‐breeding season and the breeding season period. The immunohistochemistry indicated that the abnormal triploid ovaries were dominated by small oogonium‐like cells with dense signals and that the elevated expression of activin β A and β B in the ovaries of allotriploids may be related to allotriploid sterility.

Dopamine D1 and D2 receptors mediate analgesic and hypnotic effects of l-tetrahydropalmatine in a mouse neuropathic pain model - Yuan-Yuan Liu; Tian-Xiao Wang; Ji-Chuan Zhou; Wei-Min Qu; Zhi-Li Huang (Psychopharmacology, 2019)

Using a mixture of microalgae, biochar, and organic manure to increase the capacity of soil to act as carbon sink - Jiajun Hu; Hongcheng Guo; Yiyun Xue; Min-tian Gao; Shiping Zhang; Yiu Fai Tsang; Jixiang Li; Ya-nan Wang; Lei Wang (Journal of Soils and Sediments, 2019)

Corallincola luteus sp. nov., a marine bacterium isolated from surface sediment of Bohai Sea of China - Qiaomeng Ren; Xiaoting Yang; Min Yu; Xiaorong Tian; Bei Li; Zhe Meng; Yanhong Wu; Jiwen Liu; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2019)

Religious belief and Tibetans’ response to earthquake disaster: a case study of the 2010 Ms 7.1 Yushu earthquake, Qinghai Province, China - Lei Sun; Guiwu Su; Qing Tian; Wenhua Qi; Fenggui Liu; Min Qi; Ruoyu Li (Natural Hazards, 2019)

Chemical constituents from Ginkgo biloba L. male flowers and their biological activities - Min Li; Zi-ming Xia; Bin Li; Ying Tian; Guang-jie Zhang; Chen Xu; Jun-xing Dong (Medicinal Chemistry Research, 2019)

Functional Identification of Apple MdGLK1 Which Regulates Chlorophyll Biosynthesis in Arabidopsis - Xiu-Hong An; Yi Tian; Yan-Hui Chen; En-Mao Li; Min Li; Cun-Gang Cheng (Journal of Plant Growth Regulation, 2019)

Cadmium accumulation and bioavailability in paddy soil under different water regimes for different growth stages of rice (Oryza sativa L.) - Tao Tian; Hang Zhou; Jiaofeng Gu; Runyu Jia; Hongcheng Li; Qianqian Wang; Min Zeng; Bohan Liao (Plant and Soil, 2019)

Complex rock slope deformation at Laxiwa Hydropower Station, China: background, characterization, and mechanism - Min Xia; Guang Ming Ren; Tian Bin Li; Ming Cai; Tian Jun Yang; Zong Li Wan (Bulletin of Engineering Geology and the Environment, 2019)

Identification and Characterization of ATP/ADP Isopentenyltransferases (ATP/ADP PpIPTs) Genes in Peach - Min-ji Li; Qin-ping Wei; Fu-tian Peng; Wen Yu; Jing-jing Luo; Yong-fei Zhao (Journal of Plant Growth Regulation, 2019)

Magnetotelluric signal-noise separation method based on SVM–CEEMDWT - Jin Li; Jin Cai; Jing-Tian Tang; Guang Li; Xian Zhang; Zhi-Min Xu (Applied Geophysics, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

The anxiolytic effects of Bai Le Mian capsule, a traditional Chinese hypnotic in mice - Tian-Xiao Wang; Yu-Er Wu; Wei Xu; Wan-Kun Gong; Jian Ni; Wei-Min Qu; Zhi-Li Huang (Sleep and Biological Rhythms, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Complete plastid genome of Bupleurum boissieuanum, an endemic herb plant in western China - Ying Wu; Tian-Ze Zhang; Dai-Yu Qiu; Qiang Chai; Wei-Bing Fan; Zhong-Hu Li; Min-Feng Fang (Conservation Genetics Resources, 2018)

Discovery of a novel geminivirus associated with camellia chlorotic dwarf disease - Song Zhang; Pan Shen; Min Li; Xin Tian; Changyong Zhou; Mengji Cao (Archives of Virology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Male Populus cathayana than female shows higher photosynthesis and less cellular injury through ABA-induced manganese transporting inhibition under high manganese condition - Fugui Chen; Juan Shen; Dou Min; Lixia Ke; Xin Tian; Helena Korpelainen; Chunyang Li (Trees, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Metabolic responses and “omics” technologies for elucidating the effects of heat stress in dairy cows - Li Min; Shengguo Zhao; He Tian; Xu Zhou; Yangdong Zhang; Songli Li; Hongjian Yang; Nan Zheng; Jiaqi Wang (International Journal of Biometeorology, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Characterization of a cold responsive HbICE1 gene from rubber trees - Xiao Min Deng; Jian Xiao Wang; Yan Li; Jing Wang; Wei-Min Tian (Trees, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Evaluation and quantitative analysis of different growth periods of herb–arbor intercropping systems using HPLC and UV–vis methods coupled with chemometrics - Bo-wen Chu; Ji Zhang; Zhi-min Li; Yan-li Zhao; Zhi-tian Zuo; Yuan-zhong Wang; Wan-yi Li (Journal of Natural Medicines, 2016)

Erratum to: Abyssicoccus albus gen. nov., sp. nov., a novel member of the family Staphylococcaceae isolated from marine sediment of the Indian Ocean - Zhao Jiang; Chang-Guo Yuan; Min Xiao; Xin-Peng Tian; Inam-Ullah Khan; Chang-Jin Kim; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Three new 2,5-diketopiperazines from the fish intestinal Streptomyces sp. MNU FJ-36 - Yi-xin Ou; Jia-fu Huang; Xiu-min Li; Qian-jin Kang; Yu-tian Pan (Natural Product Research, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Abyssicoccus albus gen. nov., sp. nov., a novel member of the family Staphylococcaceae isolated from marine sediment of the Indian Ocean - Zhao Jiang; Chang-Guo Yuan; Min Xiao; Xin-Peng Tian; Inam-Ullah Khan; Chang-Jin Kim; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

Genotoxicity and effect on early stage proliferation of osteoprogenitor cells on amino-group functionalized titanium implant surface: an in vitro test - Tian-qi Guo; Yi-di Zhang; Wen-jing Luo; Xue Li; Yan-min Zhou; Jing-hui Zhao (Molecular & Cellular Toxicology, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Effects of TiO2 NPs on Silkworm Growth and Feed Efficiency - YangYang Li; Min Ni; FanChi Li; Hua Zhang; KaiZun Xu; XiaoMing Zhao; JiangHai Tian; JingSheng Hu; BinBin Wang; WeiDe Shen; Bing Li (Biological Trace Element Research, 2016)

Paeoniflorin exerts analgesic and hypnotic effects via adenosine A1 receptors in a mouse neuropathic pain model - Dou Yin; Yuan-Yuan Liu; Tian-Xiao Wang; Zhen-Zhen Hu; Wei-Min Qu; Jiang-Fan Chen; Neng-Neng Cheng; Zhi-Li Huang (Psychopharmacology, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Effects of Graded Levels of Chromium Methionine on Performance, Carcass Traits, Meat Quality, Fatty Acid Profiles of Fat, Tissue Chromium Concentrations, and Antioxidant Status in Growing-Finishing Pigs - Yao-Yao Tian; Li-Min Gong; Jian-Xiang Xue; Jun Cao; Li-Ying Zhang (Biological Trace Element Research, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Union is strength: matrix elasticity and microenvironmental factors codetermine stem cell differentiation fate - Hongwei Lv; Lisha Li; Yin Zhang; Zhishen Chen; Meiyu Sun; Tiankai Xu; Licheng Tian; Man Lu; Min Ren; Yuanyuan Liu; Yulin Li (Cell and Tissue Research, 2015)

Protective effect of low dose gadolinium chloride against isoproterenol-induced myocardial injury in rat - Yuan-Yuan Zheng; Hai-Hong Zhang; Xin-Xin Yan; Min Chen; Tian-Yu Qi; Lan-E Zhang; Da-Li Luo (Apoptosis, 2015)

Effects of Titanium Dioxide Nanoparticles on the Synthesis of Fibroin in Silkworm (Bombyx mori) - Min Ni; FanChi Li; JiangHai Tian; JingSheng Hu; Hua Zhang; KaiZun Xu; BinBin Wang; YangYang Li; WeiDe Shen; Bing Li (Biological Trace Element Research, 2015)

Lampropedia puyangensis sp. nov., isolated from symptomatic bark of Populus × euramericana canker and emended description of Lampropedia hyalina (Ehrenberg 1832) Lee et al. 2004 - Yong Li; Tao Wang; Chun-gen Piao; Lai-fa Wang; Guo-zhong Tian; Tian-hui Zhu; Min-wei Guo (Antonie van Leeuwenhoek, 2015)

Silencing the Double-Stranded RNA Binding Protein DGCR8 Inhibits Ovarian Cancer Cell Proliferation, Migration, and Invasion - Yuqi Guo; Peng Tian; Chuanhe Yang; Zhibing Liang; Min Li; Michelle Sims; Lu Lu; Zhan Zhang; Hongwei Li; Lawrence M. Pfeffer; Junming Yue (Pharmaceutical Research, 2015)

Use of a New Enzyme Extraction System to Improve the Sensitivity of SOS/umu Test and Application to Environmental Samples - Zhe Tian; Yoshimitsu Oda; Yu Zhang; Min Yang; Hongyan Li (Bulletin of Environmental Contamination and Toxicology, 2015)

Effect of TiO2 Nanoparticles on the Reproduction of Silkworm - Min Ni; Fanchi Li; Binbin Wang; Kaizun Xu; Hua Zhang; Jingsheng Hu; Jianghai Tian; Weide Shen; Bing Li (Biological Trace Element Research, 2015)

Effects of Chromium Methionine Supplementation on Growth Performance, Serum Metabolites, Endocrine Parameters, Antioxidant Status, and Immune Traits in Growing Pigs - Yao-Yao Tian; Li-Ying Zhang; Bing Dong; Jun Cao; Jian-Xiang Xue; Li-Min Gong (Biological Trace Element Research, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Association Between Metabolic Syndrome and Osteoporotic Fracture in Middle-aged and Elderly Chinese Peoples - Dongchen Wang; Ning Liu; Yulei Gao; Peijia Li; Min Tian (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Impact of eddies on ocean diapycnal mixing in Gulf Stream region - Min Li; LingLing Xie; QingXuan Yang; JiWei Tian (Science China Earth Sciences, 2014)

Synthesis, Spectroscopic Properties, and Biological Applications of Eight Novel Chlorinated Fluorescent Proteins-labeling Probes - Xianglong Wu; Min Tian; Wutu Fan; Yalei Pan; Yuankun Zhai; Yinbo Niu; Chenrui Li; Tingli Lu; Qibing Mei (Journal of Fluorescence, 2014)

Comparison of lisianthus (Eustoma grandiflorum) cultivars based on the selected regeneration media using anther culture - Xuhong Zhou; Xijun Mo; Suping Qu; Min Tian; Xuewei Wu; Min Wu; Jinze Li; Ying Luo; Jihua Wang; Min Gui (Horticulture, Environment, and Biotechnology, 2014)

The distribution of four Caragana species is related to their differential responses to drought stress - Xiang-Wen Fang; Neil C. Turner; Jairo A. Palta; Ming-Xi Yu; Tian-Peng Gao; Feng-Min Li (Plant Ecology, 2014)

LPS stimulates MUC5AC expression in human biliary epithelial cells: whether there exists a possible pathway of PKC/NADPH/ROS? - Min Li; Yu Tian; Shuodong Wu; Hong Yu; Yongnan Li (Molecular and Cellular Biochemistry, 2014)

Expression of SbSNAC1, a NAC transcription factor from sorghum, confers drought tolerance to transgenic Arabidopsis - Min Lu; Deng-Feng Zhang; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Climate change trend in China, with improved accuracy - Tian-Xiang Yue; Na Zhao; R. Douglas Ramsey; Chen-Liang Wang; Ze-Meng Fan; Chuan-Fa Chen; Yi-Min Lu; Bai-Lian Li (Climatic Change, 2013)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Shifts in microbial community composition and function in the acidification of a lead/zinc mine tailings - Lin‐xing Chen; Jin‐tian Li; Ya‐ting Chen; Li‐nan Huang; Zheng‐shuang Hua; Min Hu; Wen‐sheng Shu (Environmental Microbiology, 2013)
Summary In an attempt to link the microbial community composition and function in mine tailings to the generation of acid mine drainage, we simultaneously explored the geochemistry and microbiology of six tailings collected from a lead/zinc mine, i.e. primary tailings ( T 1), slightly acidic tailings ( T2 ), extremely acidic tailings ( T 3, T 4 and T 5) and orange‐coloured oxidized tailings ( T6 ). Geochemical results showed that the six tailings (from T 1 to T 6) likely represented sequential stages of the acidification process of the mine tailings. 16 S r RNA pyrosequencing revealed a contrasting microbial composition between the six tailings: P roteobacteria‐ related sequences dominated T 1– T 3 with relative abundance ranging from 56 to 93%, whereas F erroplasma‐ related sequences dominated T 4– T 6 with relative abundance ranging from 28 to 58%. Furthermore, metagenomic analysis of the microbial communities of T 2 and T 6 indicated that the genes encoding key enzymes for microbial carbon fixation, nitrogen fixation and sulfur oxidation in T 2 were largely from T hiobacillus and A cidithiobacillus , M ethylococcus capsulatus , and T hiobacillus denitrificans respectively; while those in T 6 were mostly identified in A cidithiobacillus and L eptospirillum , A cidithiobacillus and L eptospirillum , and A cidithiobacillus respectively. The microbial communities in T 2 and T 6 harboured more genes suggesting diverse metabolic capacities for sulfur oxidation/heavy metal detoxification and tolerating low pH respectively.

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Expression of Immune Molecules CD25 and CXCL13 Correlated with Clinical Severity of Myasthenia Gravis - Min Zhang; Jun Guo; Hongzeng Li; Yongan Zhou; Feng Tian; Li Gong; Xianni Wang; Zhuyi Li; Wei Zhang (Journal of Molecular Neuroscience, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

A maize stress-responsive NAC transcription factor, ZmSNAC1, confers enhanced tolerance to dehydration in transgenic Arabidopsis - Min Lu; Sheng Ying; Deng-Feng Zhang; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell Reports, 2012)

A new model for cation exchange equilibrium considering the electrostatic field of charged particles - Xin Min Liu; Hang Li; Rui Li; Rui Tian; Jie Hou (Journal of Soils and Sediments, 2012)

Paenibacillus frigoriresistens sp. nov., a novel psychrotroph isolated from a peat bog in Heilongjiang, Northern China - Hong Ming; Guo-Xing Nie; Hong-Chen Jiang; Tian-Tian Yu; En-Min Zhou; Hui-Gen Feng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Kineococcus glutineturens sp. nov., isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Jing Zhang; Hui-Gen Feng; Shuai Li; Tian-Tian Yu; En-Min Zhou; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Thermoactinospora rubra gen. nov., sp. nov., a thermophilic actinomycete isolated from Tengchong, Yunnan province, south–west China - En-Min Zhou; Shu-Kun Tang; Carsten Sjøholm; Zhao-Qi Song; Tian-Tian Yu; Ling-Ling Yang; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Geodermatophilus nigrescens sp. nov., isolated from a dry-hot valley - Guo-Xing Nie; Hong Ming; Shuai Li; En-Min Zhou; Juan Cheng; Tian-Tian Yu; Jing Zhang; Hui-Gen Feng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Molecular characterization of a novel 14-3-3 protein gene (Hb14-3-3c) from Hevea brasiliensis - Zi-Ping Yang; Hui-Liang Li; Dong Guo; Wei-Min Tian; Shi-Qing Peng (Molecular Biology Reports, 2012)

Characterization of HbEREBP1, a wound-responsive transcription factor gene in laticifers of Hevea brasiliensis Muell. Arg. - Yue-Yi Chen; Li-Feng Wang; Long-Jun Dai; Shu-Guang Yang; Wei-Min Tian (Molecular Biology Reports, 2012)

Functional MRI mapping of category-specific sites associated with naming of famous faces, animals and man-made objects - Hong-Min Bai; Tao Jiang; Wei-Min Wang; Tian-Dong Li; Yan Liu; Yi-Cheng Lu (Neuroscience Bulletin, 2011)

Enhanced rapamycin production in Streptomyces hygroscopicus by integrative expression of aveR, a LAL family transcriptional regulator - Minhong Huang; Min Li; Zhixiang Feng; Yang Liu; Yiwen Chu; Yongqiang Tian (World Journal of Microbiology and Biotechnology, 2011)

Comparative studies on tolerance of Medicago truncatula and Medicago falcata to freezing - Li-Li Zhang; Min-Gui Zhao; Qiu-Ying Tian; Wen-Hao Zhang (Planta, 2011)

Isolation and promoter analysis of a chalcone synthase gene PtrCHS4 from Populus trichocarpa - Yiming Sun; Qiaoyan Tian; Li Yuan; Yuanzhong Jiang; Yan Huang; Min Sun; Shaohu Tang; Keming Luo (Plant Cell Reports, 2011)

Protein differential expression in the latex from Hevea brasiliensis between self-rooting juvenile clones and donor clones - Hui-Liang Li; Dong Guo; Fang-Ying Lan; Wei-Min Tian; Shi-Qing Peng (Acta Physiologiae Plantarum, 2011)

Three MADS-box genes of Hevea brasiliensis expressed during somatic embryogenesis and in the laticifer cells - Hui-Liang Li; Ying Wang; Dong Guo; Wei-Min Tian; Shi-Qing Peng (Molecular Biology Reports, 2011)

Serum biochemical analysis to indicate pathogenic risk on mouse Mus musculus exposure to source of drinking water - Shi Feng Yun; Xiao Yun Tian; Shu Pei Cheng; Yan Zhang; Ai Min Li; Li Bo Zhang; Xu Xiang Zhang; Li Chen; Bing Wu; Lian Qin Guo; Yun Zhong Shi (Ecotoxicology, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Molecular characterization of a thioredoxin h gene (HbTRX1) from Hevea brasiliensis showing differential expression in latex between self-rooting juvenile clones and donor clones - Hui-Liang Li; Hui-Zhong Lu; Dong Guo; Wei-Min Tian; Shi-Qing Peng (Molecular Biology Reports, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Seasonal and Spatial Variations of Air Concentrations of Polycyclic Aromatic Hydrocarbons in Northeastern Chinese Urban Region - Wan-li Ma; Hong Qi; Yi-fan Li; Li-yan Liu; De-zhi Sun; De-gao Wang; Zhi Zhang; Chong-guo Tian; Ji-min Shen (Bulletin of Environmental Contamination and Toxicology, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Assessing the combination effects of environmental estrogens in fish - Hui Zhang; Fan-Xiang Kong; Yang Yu; Xiao-Li Shi; Min Zhang; Hong-Er Tian (Ecotoxicology, 2010)

Studies on morphology and aristolochic acid analogue constituents of Asarum campaniflorum and a comparison with two official species of Asari Radix et Rhizoma - Yao-Li Li; Min Tian; Jie Yu; Ming-Ying Shang; Shao-Qing Cai (Journal of Natural Medicines, 2010)

Epidemic risk analysis after the Wenchuan Earthquake using remote sensing - Chunxiang Cao; Chaoyi Chang; Min Xu; Jian Zhao; Mengxu Gao; Hao Zhang; Jianping Guo; Jianghong Guo; Lei Dong; Qisheng He; Linyan Bai; Yunfei Bao; et al. (International Journal of Remote Sensing, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

Enterobacter spp.: A new evidence causing bacterial wilt on mulberry - Bo Zhu; GuoFen Wang; GuanLin Xie; Qin Zhou; Min Zhao; Kawicha Praphat; Bin Li; WenXiao Tian (Science China Life Sciences, 2010)

Aβ31–35-induced neuronal apoptosis is mediated by JNK-dependent extrinsic apoptosis pathway - Ling-Min Li; Qing-Hua Liu; Jian-Tian Qiao; Ce Zhang (Neuroscience Bulletin, 2009)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Relationships between endothelial nitric oxide synthase gene polymorphisms and osteoporosis in postmenopausal women - Shun-zhi Liu; Hong Yan; Wei-kun Hou; Peng Xu; Juan Tian; Li-fang Tian; Bo-feng Zhu; Jie Ma; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2009)

Genetic basis of nutritional content of stover in maize under low nitrogen conditions - Hui-ling Xie; Hong-qiang Ji; Zong-hua Liu; Guo-wei Tian; Chun-li Wang; Yan-min Hu; Ji-hua Tang (Euphytica, 2009)

Determination of Alkyl Polycyclic Aromatic Hydrocarbons in Dustfall by Supercritical Fluid Extraction Followed by Gas Chromatography/Mass Spectrum - Jin-Jun Lian; Chun-Lei Li; Yu Ren; Tian-Tao Cheng; Jian-Min Chen (Bulletin of Environmental Contamination and Toxicology, 2009)

Cloning and characterization of a novel cysteine protease gene (HbCP1) from Hevea brasiliensis - Shi-Qing Peng; Jia-Hong Zhu; Hui-Liang Li; Wei-Min Tian (Journal of Biosciences, 2008)

Differential generation of hydrogen peroxide upon exposure to zinc and cadmium in the hyperaccumulating plant specie (Sedum alfredii Hance) - Yue-En Chao; Min Zhang; Sheng-ke Tian; Ling-li Lu; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Caspase-3 antisense oligodeoxynucleotides inhibit apoptosis in γ-irradiated human leukemia HL-60 cells - Xiao-Tian Zhang; Tian-Bao Song; Bao-Ling Du; Dong-Min Li; Xiao-Ming Li (Apoptosis, 2007)

Isolation of a human gallbladder cancer cell clone with high invasive phenotype in vitro and metastatic potential in orthotopic model and inhibition of its invasiveness by heparanase antisense oligodeoxynucleotides - Xin-Zhong Chang; Zhan-Min Wang; Jin-Ming Yu; Fu-Guo Tian; Wei Jin; Yi Zhang; Jie Yu; Lian-Fang Li; Xiao-Feng Liu; Zhi-Wei Li; Zhi-Min Shao (Clinical & Experimental Metastasis, 2007)

Gender-specific associations between MICA-STR and nasopharyngeal carcinoma in a southern Chinese Han population - Wei Tian; Xiao-min Zeng; Li-xin Li; He-kun Jin; Qi-zhi Luo; Fan Wang; Shi-shi Guo; Ya Cao (Immunogenetics, 2006)

Human Multidrug Resistance Associated Protein 4 Confers Resistance to Camptothecins - Quan Tian; Jing Zhang; Theresa May Chin Tan; Eli Chan; Wei Duan; Sui Yung Chan; Urs Alex Boelsterli; Paul Chi-Lui Ho; Hongyuan Yang; Jin-Song Bian; Min Huang; Yi-Zhun Zhu; et al. (Pharmaceutical Research, 2005)

Aluminum content of tea leaves and factors affecting the uptake of aluminum from soil into tea leaves - Zhong-lei Xie; De-ming Dong; Guo-zhang Bao; Sheng-tian Wang; Yao-guo Du; Li-min Qiu (Chinese Geographical Science, 2001)

The types of lake in Songnen Plain and their regional character - Jin-fu Lu; Dong-mei Jie; Zhi-min Li; Xue-tian Leng (Chinese Geographical Science, 2000)